Photosensitive glass and photosensitive glass-ceramics

CN118598510BActive Publication Date: 2026-10-27CDGM GLASS LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410784178.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-04-22
Filing Date
2024-06-18
Publication Date
2026-10-27
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

现有技术中的光敏玻璃线膨胀系数较高,玻璃经过掩膜曝光及热处理后,获得的光敏微晶玻璃形成的图案精度较差;同时其机械性能也难以满足高性能电子设备等的使用

Benefits of technology

[0080]本发明的有益效果是:通过合理的组分设计,本发明的光敏玻璃具有较低的线膨胀系数;光敏玻璃经过掩膜曝光及热处理后,获得的光敏微晶玻璃形成的图案精度较高。本发明光敏微晶玻璃和光敏微晶玻璃制品具有优异机械性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004898105950000221
    Figure BDA0004898105950000221
  • Figure BDA0004898105950000261
    Figure BDA0004898105950000261
  • Figure BDA0004898105950000271
    Figure BDA0004898105950000271
Patent Text Reader

Abstract

The application provides a photosensitive glass, which comprises the following components in percentage by weight: SiO2: 65-78%; ZrO2: 1.5-10%; R2O+Li2O+Al2O3: 15-30%; CeO2: 0.01-0.6%; Ag2O: 0.01-0.8%; Sb2O3+SnO2: 0.05-1.2%, wherein ZrO2 / (Ag2O+CeO2) is 2.3-50.0, and the R2O is one or both of Na2O and K2O. Through reasonable component design, the photosensitive glass has a low linear expansion coefficient; after mask exposure and heat treatment, the photosensitive microcrystalline glass obtained has high pattern precision. The photosensitive microcrystalline glass and the photosensitive microcrystalline glass product have excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a photosensitive glass, and more particularly to a photosensitive glass having a low coefficient of linear expansion, and photosensitive microcrystalline glass made therefrom. Background Technology

[0002] In recent years, glass materials have been widely used in various displays and display devices of many electronic products, such as mobile phones, music players, e-book readers, notebooks, tablets, laptops, ATMs, and other similar devices. The protective materials used to form the casings of display devices and electronic devices are typically selected to meet the mechanical requirements associated with the end-use of the electronic device. With the diversification of market demands, the application scenarios of protective glass materials are becoming increasingly complex, and their role is no longer limited to protecting internal electronic components; sometimes, they also need to perform other functions. For example, in the vital sign monitoring of smartwatches, the glass material needs to be partially transparent, but in other areas, it needs to block light to avoid interference from stray light. Therefore, the glass material needs to have both black and transparent parts, which poses new challenges to glass manufacturing technology. In existing technologies, the aforementioned cover material can be manufactured using two different materials, transparent and black, through an embedded design. However, due to the different strengths and large differences in the coefficients of thermal expansion between the two materials, and the need to process through holes, micro-cracks exist on the inner wall of the glass, leading to a reduction in the strength of the cover material. Processing smaller holes or irregular shapes is difficult, and the manufacturing cost is high.

[0003] Photosensitive microcrystalline glass is a type of glass that undergoes structural changes within its body under ultraviolet light irradiation, generating crystal nuclei. Further heat treatment at a specific temperature results in the formation of numerous specific crystals in the irradiated area. The exposed portions exhibit high crystallinity, a darker glass color, and reduced light transmittance, while the unexposed portions remain transparent, preventing crystallization. Therefore, mask exposure can be used to achieve simultaneous black and transparent portions within the glass material. However, current photosensitive glass technologies suffer from high coefficients of linear expansion, resulting in poor pattern precision after mask exposure and heat treatment. Furthermore, their mechanical properties are insufficient for use in high-performance electronic devices. Summary of the Invention

[0004] Based on the above reasons, the technical problem to be solved by the present invention is to provide a photosensitive glass with a low coefficient of linear expansion. After the photosensitive glass is exposed by a mask and heat-treated, the pattern formed by the photosensitive microcrystalline glass is of high precision.

[0005] The present invention also provides a photosensitive microcrystalline glass and a photosensitive microcrystalline glass product with excellent mechanical properties.

[0006] The solution adopted by this invention to solve the technical problem is:

[0007] (1) Photosensitive glass, the composition of which is expressed by weight percentage as follows: SiO2: 65-78%; ZrO2: 1.5-10%; R2O+Li2O+Al2O3: 15-30%; CeO2: 0.01-0.6%; Ag2O: 0.01-0.8%; Sb2O3+SnO2: 0.05-1.2%, wherein ZrO2 / (Ag2O+CeO2) is 2.3-50.0, and the R2O is one or both of Na2O and K2O.

[0008] (2) Photosensitive glass, the composition of which is expressed by weight percentage as follows: SiO2: 65-78%; ZrO2: 1.5-10%; R2O+Li2O+Al2O3: 15-30%; CeO2: 0.01-0.6%; Ag2O: 0.01-0.8%; Sb2O3+SnO2: 0.05-1.2%, wherein R2O is one or both of Na2O and K2O.

[0009] (3) The photosensitive glass according to (1) or (2) further contains, by weight percentage: Ln2O3: 0-5%; and / or Fe2O3: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0010] (4) A photosensitive glass, comprising SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2, and Ag2O, wherein the composition is expressed as a weight percentage, and the ratio of ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, wherein the R2O is one or both of Na2O and K2O, and the coefficient of linear expansion α of the photosensitive glass is... 20℃-300℃ 100×10 -7 / ℃ below.

[0011] (5) Photosensitive glass, which contains SiO2, R2O, Li2O, Al2O3 and ZrO2, and its composition is expressed as a weight percentage, of which: SiO2 / Li2O is 5.5 to 10.0.

[0012] (6) Photosensitive glass, which contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O. The composition, expressed as a weight percentage, contains Sb2O3+SnO2: 0.05-1.2%, of which (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0-30.0.

[0013] (7) Photosensitive glass, whose composition contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, and whose Young's modulus E is 7000×10⁻⁶. 7Pa ~ 9500 × 10 7 Pa.

[0014] (8) A photosensitive glass, the composition of which contains SiO2, R2O, Li2O, Al2O3 and ZrO2, wherein the dielectric constant ε of the photosensitive glass is... r The value ranges from 5.5 to 8.5.

[0015] (9) Photosensitive glass, which contains SiO2, R2O, Li2O, Al2O3 and ZrO2, and its composition is expressed as a weight percentage, of which (SiO2+Li2O) / ZrO2 is 8.0 to 55.0.

[0016] (10) The photosensitive glass according to any one of (4) to (9) contains, by weight percentage: SiO2: 65-78%; and / or R2O+Li2O+Al2O3: 15-30%; and / or ZrO2: 1.5-10%; and / or CeO2: 0.01-0.6%; and / or Ag2O: 0.01-0.8%; and / or Sb2O3+SnO2: 0.05-1.2%; and / or Ln2O3: 0-5%; and / or Fe2O3: 0-1%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0017] (11) The photosensitive glass according to any one of (1) to (10), wherein its components are expressed as weight percentages, wherein: SiO2 / Li2O is 5.5 to 10.0, preferably SiO2 / Li2O is 6.0 to 9.0, more preferably SiO2 / Li2O is 7.0 to 8.5; and / or (K2O+Na2O) / ZrO2 is 0.5 to 7.1, preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, more preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5; and / or Li2O / ZrO2 is 1.0 to 7.5, preferably Li2O / ZrO2 is 1.2 to 5.0, more preferably Li2O / ZrO2 is 1.4 to 4.3, and even more preferably Li2O / ZrO2 is 1.6 to 3.0; and / or (SiO2 The ratio of (SiO2+Li2O) / ZrO2 is 8.0–55.0, preferably 10.0–37.0, more preferably 12.0–25.0, and even more preferably 13.0–20.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0–7.5, preferably 3.7–6.5, more preferably 4.3–6.0, and even more preferably 4.8–5.8.

[0018] (12) The photosensitive glass according to any one of (1) to (11) has the following components expressed as weight percentages: (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, more preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; and / or Ag2O / CeO2 is 1. 0–10.0, preferably Ag₂O / CeO₂ is 1.5–6.5, more preferably Ag₂O / CeO₂ is 2.0–4.5; and / or ZrO₂ / (Ag₂O+CeO₂) is 6.5–35.0, preferably ZrO₂ / (Ag₂O+CeO₂) is 8.5–20.0, more preferably ZrO₂ / (Ag₂O+CeO₂) is 11.0–18.0; and / or The ratio of (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0 to 30.0, preferably 3.0 to 20.0, more preferably 5.0 to 12.5, and even more preferably 7.5 to 10.0. And / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.0, preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4 to 5.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.7, and even more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.2.

[0019] (13) The photosensitive glass according to any one of (1) to (12), wherein the components are expressed as weight percentages, wherein: SiO2: 68-77%, preferably SiO2: 69.5-75.5%; and / or R2O+Li2O+Al2O3: 17.5-29.5%, preferably R2O+Li2O+Al2O3: 18.5-26%, more preferably R2O+Li2O+Al2O3: 20-25%; and / or ZrO2: 2-8%, preferably ZrO2: 3-6.5%; and / or CeO2: 0.07-0.4%, preferably CeO2: 0.08-0.3%. R2O: 0.1-0.6%, preferably 0.2-0.5%; and / or Sb2O3+SnO2: 0.1-1%, preferably 0.2-0.7%; and / or Ln2O3: 0-3%, preferably 0-1%, more preferably without Ln2O3; and / or Fe2O3: 0-0.5%, preferably 0-0.2%, more preferably without Fe2O3, wherein R2O is one or both of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0020] (14) The photosensitive glass according to any one of (1) to (13), wherein the components are expressed in weight percentage, wherein: R2O: 2-12%, preferably R2O: 3-10%, more preferably R2O: 4-8%; and / or Li2O: 5-15%, preferably Li2O: 7-13%, more preferably Li2O: 8.5-12%; and / or Al2O3: 3-12%, preferably Al2O3: 4-10%, more preferably Al2O3: 5-9%; and / or Sb2O3: 0-1%, preferably Sb2O3: 0.01-0.7%, more preferably Sb2O3: 0.07-0.5%; and / or SnO2: 0-0.5%, preferably SnO2: 0-0.3%, more preferably SnO2: 0-0.2%.

[0021] (15) The photosensitive glass according to any one of (1) to (14), wherein the refractive index n of the photosensitive glass is d The value is 1.51–1.55, preferably 1.52–1.54, more preferably 1.53–1.535, and even more preferably 1.53112–1.53284; and / or the Young's modulus E is 7000 × 10⁻⁶. 7 Pa ~ 9500 × 10 7 Pa, preferably 7500 × 10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa ~ 9014 × 10 7 Pa, more preferably 8005 × 10 7 Pa~8488×10 7 Pa; and / or Knoop hardness Hk 0.1 450 kgf / mm 2 The above values ​​are preferably 470–600 kgf / mm². 2 More preferably, it is 480–582 kgf / mm 2 More preferably, it is 492–532 kgf / mm 2 ; and / or the drop ball test height I is 200 mm or more, preferably 300 mm or more, more preferably 400 mm or more; and / or the dielectric loss tanδ is 11.0 × 10⁻⁶. -3 The preferred value is 7.0×10. -3 ~10.5×10 -3 More preferably 7.2×10 -3 ~9.8×10 -3 Further preferred is 7.4×10 -3 ~9.2×10 -3 ; and / or dielectric constant ε rThe coefficient of linear expansion is 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and even more preferably 6.3 to 7.0; and / or the coefficient of linear expansion α. 20℃-300℃ 100×10 -7 Below / ℃, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, further preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0022] (16) Photosensitive microcrystalline glass, the composition of which, expressed by weight percentage, contains: SiO2: 65-78%; ZrO2: 1.5-10%; R2O+Li2O+Al2O3: 15-30%; CeO2: 0.01-0.6%; Ag2O: 0.01-0.8%; Sb2O3+SnO2: 0.05-1.2%, wherein ZrO2 / (Ag2O+CeO2) is 2.3-50.0, and the R2O is one or both of Na2O and K2O.

[0023] (17) Photosensitive microcrystalline glass, the composition of which, expressed by weight percentage, contains: SiO2: 65-78%; ZrO2: 1.5-10%; R2O+Li2O+Al2O3: 15-30%; CeO2: 0.01-0.6%; Ag2O: 0.01-0.8%; Sb2O3+SnO2: 0.05-1.2%, wherein the R2O is one or both of Na2O and K2O.

[0024] (18) The photosensitive microcrystalline glass according to (16) or (17) further contains, by weight percentage: Ln2O3: 0-5%; and / or Fe2O3: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0025] (19) A photosensitive microcrystalline glass, the composition of which contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, the composition is expressed as a weight percentage, wherein ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, and the R2O is one or two of Na2O and K2O.

[0026] (20) A photosensitive microcrystalline glass, the composition of which contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, the composition is expressed as a weight percentage, wherein: (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5, and the R2O is one or two of Na2O and K2O.

[0027] (21) Photosensitive microcrystalline glass, the composition of which contains SiO2, R2O, Li2O, Al2O3 and ZrO2, the composition is expressed as a weight percentage, wherein (K2O+Na2O) / ZrO2 is 0.5 to 7.1, and the R2O is one or two of Na2O and K2O.

[0028] (22) Photosensitive microcrystalline glass, which contains SiO2, Li2O, Al2O3 and ZrO2, and its composition is expressed as a weight percentage, wherein: SiO2 / Li2O is 5.5 to 10.0.

[0029] (23) Photosensitive microcrystalline glass, the composition of which contains SiO2, Li2O, Al2O3, CeO2 and Ag2O, and the composition expressed by weight percentage contains Sb2O3+SnO2: 0.05~1.2%, of which: (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0~30.0.

[0030] (24) Photosensitive microcrystalline glass, the composition of which contains SiO2, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, and the composition expressed by weight percentage contains Sb2O3+SnO2: 0.05~1.2%, of which: (Sb2O3+SnO2) / Ag2O is 0.1~5.0.

[0031] (25) A photosensitive microcrystalline glass, the composition of which contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, the composition expressed by weight percentage, contains Sb2O3+SnO2: 0.05~1.2%, wherein: (Sb2O3+SnO2+CeO2) / Ag2O is 0.1~10.0, and the R2O is one or two of Na2O and K2O.

[0032] (26) A photosensitive microcrystalline glass comprising one or more blackened portions and one or more transparent portions, wherein the photosensitive microcrystalline glass contains a lithium metasilicate crystalline phase, and the weight percentage of the lithium metasilicate crystalline phase in the blackened portion of the photosensitive microcrystalline glass is 5 to 50%.

[0033] (27) A photosensitive microcrystalline glass, the composition of which contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, wherein R2O is one or two of Na2O and K2O, and the photosensitive microcrystalline glass comprises one or more blackened portions and one or more transparent portions.

[0034] (28) A photosensitive microcrystalline glass comprising one or more blackened portions and one or more transparent portions, wherein the transmittance T of the blackened portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass at 870 nm is... 870nm It is below 15.0%.

[0035] (29) A photosensitive microcrystalline glass, wherein the photosensitive microcrystalline glass contains a lithium metasilicate phase, the lithium metasilicate phase having a higher weight percentage than other phases.

[0036] (30) The photosensitive microcrystalline glass according to any one of (19) to (29) contains, by weight percentage: SiO2: 65-78%; and / or R2O+Li2O+Al2O3: 15-30%; and / or ZrO2: 1.5-10%; and / or CeO2: 0.01-0.6%; and / or Ag2O: 0.01-0.8%; and / or Sb2O3+SnO2: 0.05-1.2%; and / or Ln2O3: 0-5%; and / or Fe2O3: 0-1%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0037] (31) The photosensitive microcrystalline glass according to any one of (16) to (30), wherein the composition is expressed as a weight percentage, wherein: SiO2 / Li2O is 5.5 to 10.0, preferably SiO2 / Li2O is 6.0 to 9.0, more preferably SiO2 / Li2O is 7.0 to 8.5; and / or (K2O+Na2O) / ZrO2 is 0.5 to 7.1, preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, more preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5; and / or Li2O / ZrO2 is 1.0 to 7.5, preferably Li2O / ZrO2 is 1.2 to 5.0, more preferably Li2O / ZrO2 is 1.4 to 4.3, and even more preferably Li2O / ZrO2 is 1.6 to 3.0; and / or (SiO2 / Li2O) / ZrO2 ... The ratio of (SiO2+Li2O) / ZrO2 is 8.0 to 55.0, preferably 10.0 to 37.0, more preferably 12.0 to 25.0, and even more preferably 13.0 to 20.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5, preferably 3.7 to 6.5, more preferably 4.3 to 6.0, and even more preferably 4.8 to 5.8.

[0038] (32) The photosensitive microcrystalline glass according to any one of (16) to (31), wherein the composition is expressed as a weight percentage, wherein: (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, more preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; and / or Ag2O / CeO2 is... 1.0–10.0, preferably Ag₂O / CeO₂ is 1.5–6.5, more preferably Ag₂O / CeO₂ is 2.0–4.5; and / or ZrO₂ / (Ag₂O+CeO₂) is 6.5–35.0, preferably ZrO₂ / (Ag₂O+CeO₂) is 8.5–20.0, more preferably ZrO₂ / (Ag₂O+CeO₂) is 11.0–18.0; and / Alternatively, the ratio of (Ag₂O+SnO₂+Sb₂O₃) / CeO₂ can be 1.0–30.0, preferably 3.0–20.0, more preferably 5.0–12.5, and even more preferably 7.5–10.0. ; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.0, preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4 to 5.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.7, and even more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.2.

[0039] (33) The photosensitive microcrystalline glass according to any one of (16) to (32), wherein the components are expressed as weight percentages, wherein: SiO2: 68-77%, preferably SiO2: 69.5-75.5%; and / or R2O+Li2O+Al2O3: 17.5-29.5%, preferably R2O+Li2O+Al2O3: 18.5-26%, more preferably R2O+Li2O+Al2O3: 20-25%; and / or ZrO2: 2-8%, preferably ZrO2: 3-6.5%; and / or CeO2: 0.07-0.4%, preferably CeO2: 0.08-0.3%. %; and / or Ag2O: 0.1-0.6%, preferably Ag2O: 0.2-0.5%; and / or Sb2O3+SnO2: 0.1-1%, preferably Sb2O3+SnO2: 0.2-0.7%; and / or Ln2O3: 0-3%, preferably Ln2O3: 0-1%, more preferably not containing Ln2O3; and / or Fe2O3: 0-0.5%, preferably Fe2O3: 0-0.2%, more preferably not containing Fe2O3, wherein R2O is one or both of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0040] (34) The photosensitive microcrystalline glass according to any one of (16) to (33), wherein the components are expressed in weight percentage, wherein: R2O: 2-12%, preferably R2O: 3-10%, more preferably R2O: 4-8%; and / or Li2O: 5-15%, preferably Li2O: 7-13%, more preferably Li2O: 8.5-12%; and / or Al2O3: 3-12%, preferably Al2O3: 4-10%, more preferably Al2O3: 5-9%; and / or Sb2O3: 0-1%, preferably Sb2O3: 0.01-0.7%, more preferably Sb2O3: 0.07-0.5%; and / or SnO2: 0-0.5%, preferably SnO2: 0-0.3%, more preferably SnO2: 0-0.2%.

[0041] (35) The photosensitive microcrystalline glass according to any one of (16) to (34), wherein the photosensitive microcrystalline glass comprises one or more blackened portions and one or more transparent portions; or the photosensitive microcrystalline glass is entirely composed of blackened portions.

[0042] (36) The photosensitive microcrystalline glass according to any one of (16) to (35) wherein the blackened portion contains a crystalline phase and the transparent portion does not contain a crystalline phase.

[0043] (37) The photosensitive glass-ceramic according to any one of (16) to (36), wherein the photosensitive glass-ceramic contains a lithium silicate phase, preferably a lithium metasilicate phase, more preferably the lithium metasilicate phase has a weight percentage of 5 to 50% in the blackened portion of the photosensitive glass-ceramic, even more preferably the lithium metasilicate phase has a weight percentage of 5 to 40% in the blackened portion of the photosensitive glass-ceramic, and even more preferably the lithium metasilicate phase has a weight percentage of 10 to 30% in the blackened portion of the photosensitive glass-ceramic.

[0044] (38) The photosensitive microcrystalline glass according to any one of (16) to (37), the average transmittance T of the transparent portion of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm in the 400 to 800 nm wavelength range. 400-800nm The transmittance is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and even more preferably 91.5 to 95.0%; and / or the average transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm in the 400 to 800 nm wavelength range. 400- 800nm The transmittance T of the blackened portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass at 870 nm is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, even more preferably 1.2% or less, and still more preferably 0.5% or less; and / or the transmittance T of the blackened portion of the photosensitive microcrystalline glass at 870 nm. 870nm The transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm at 940 nm is 15.0% or less, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and even more preferably 0.1 to 5.0%; and / or the transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm. 940nm The content is 50.0% or less, preferably 0.1% to 35.0%, more preferably 0.3% to 20.0%, even more preferably 0.3% to 15.0%, and even more preferably 0.3% to 10.0%.

[0045] (39) The photosensitive microcrystalline glass according to any one of (16) to (38) has a thickness of 0.5 to 1.5 mm, preferably 0.8 to 1.2 mm, and more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0046] (40) A photosensitive microcrystalline glass product, the composition of which, expressed by weight percentage, contains: SiO2: 65-78%; ZrO2: 1.5-10%; R2O+Li2O+Al2O3: 15-30%; CeO2: 0.01-0.6%; Ag2O: 0.01-0.8%; Sb2O3+SnO2: 0.05-1.2%, wherein ZrO2 / (Ag2O+CeO2) is 2.3-50.0, and the R2O is one or both of Na2O and K2O.

[0047] (41) A photosensitive microcrystalline glass product, the composition of which, expressed by weight percentage, contains: SiO2: 65-78%; ZrO2: 1.5-10%; R2O+Li2O+Al2O3: 15-30%; CeO2: 0.01-0.6%; Ag2O: 0.01-0.8%; Sb2O3+SnO2: 0.05-1.2%, wherein the R2O is one or both of Na2O and K2O.

[0048] (42) The photosensitive microcrystalline glass product according to (40) or (41) further contains, by weight percentage: Ln2O3: 0-5%; and / or Fe2O3: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0049] (43) A photosensitive microcrystalline glass product, the composition of which contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, the composition is expressed as a weight percentage, wherein ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, and the R2O is one or two of Na2O and K2O.

[0050] (44) Photosensitive microcrystalline glass products containing SiO2, Li2O, Al2O3 and ZrO2, the composition of which is expressed as a weight percentage, wherein: SiO2 / Li2O is 5.5 to 10.0.

[0051] (45) Photosensitive microcrystalline glass products containing SiO2, Li2O, Al2O3 and ZrO2, the composition of which is expressed as a weight percentage, wherein (SiO2+Li2O) / ZrO2 is 8.0 to 55.0.

[0052] (46) Photosensitive microcrystalline glass products containing SiO2, R2O, Li2O, Al2O3 and ZrO2, the composition of which is expressed as a weight percentage, wherein (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5.

[0053] (47) Photosensitive microcrystalline glass products containing SiO2, Li2O, Al2O3, CeO2 and Ag2O, and the composition expressed as a weight percentage, containing Sb2O3+SnO2: 0.05 to 1.2%, of which (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0.

[0054] (48) Photosensitive microcrystalline glass products containing SiO2, Li2O, Al2O3, CeO2 and Ag2O, and the composition expressed by weight percentage, containing Sb2O3+SnO2: 0.05~1.2%, of which: Ag2O / CeO2 is 1.0~10.0.

[0055] (49) Photosensitive microcrystalline glass products containing SiO2, Li2O, Al2O3, CeO2 and Ag2O, and the composition expressed by weight percentage, containing Sb2O3+SnO2: 0.05~1.2%, of which: (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0~30.0.

[0056] (50) A photosensitive microcrystalline glass product comprising one or more blackened portions and one or more transparent portions, wherein the photosensitive microcrystalline glass product contains a lithium metasilicate crystalline phase, and the weight percentage of the lithium metasilicate crystalline phase in the blackened portion of the photosensitive microcrystalline glass product is 5 to 50%.

[0057] (51) A photosensitive microcrystalline glass product, the composition of which contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, wherein R2O is one or two of Na2O and K2O, and the photosensitive microcrystalline glass product comprises one or more blackened portions and one or more transparent portions.

[0058] (52) A photosensitive microcrystalline glass product, the composition of which contains SiO2, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, wherein R2O is one or two of Na2O and K2O, and the drop ball test height II of the photosensitive microcrystalline glass product is 800mm or more.

[0059] (53) The photosensitive microcrystalline glass product according to any one of (43) to (52) contains, by weight percentage: SiO2: 65-78%; and / or R2O+Li2O+Al2O3: 15-30%; and / or ZrO2: 1.5-10%; and / or CeO2: 0.01-0.6%; and / or Ag2O: 0.01-0.8%; and / or Sb2O3+SnO2: 0.05-1.2%; and / or Ln2O3: 0-5%; and / or Fe2O3: 0-1%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0060] (54) The photosensitive microcrystalline glass article according to any one of (40) to (53), wherein the components are expressed as weight percentages, wherein: SiO2 / Li2O is 5.5 to 10.0, preferably SiO2 / Li2O is 6.0 to 9.0, more preferably SiO2 / Li2O is 7.0 to 8.5; and / or (K2O+Na2O) / ZrO2 is 0.5 to 7.1, preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, more preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5; and / or Li2O / ZrO2 is 1.0 to 7.5, preferably Li2O / ZrO2 is 1.2 to 5.0, more preferably Li2O / ZrO2 is 1.4 to 4.3, and even more preferably Li2O / ZrO2 is 1.6 to 3.0; and / or (Si The ratio of (SiO2+Li2O) / (ZrO2) is 8.0–55.0, preferably 10.0–37.0, more preferably 12.0–25.0, and even more preferably 13.0–20.0; and / or the ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0–7.5, preferably 3.7–6.5, more preferably 4.3–6.0, and even more preferably 4.8–5.8.

[0061] (55) The photosensitive microcrystalline glass article according to any one of (40) to (54), wherein the components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, more preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; and / or Ag2O / CeO2 The ratio is 1.0 to 10.0, preferably Ag₂O / CeO₂ is 1.5 to 6.5, more preferably Ag₂O / CeO₂ is 2.0 to 4.5; and / or ZrO₂ / (Ag₂O+CeO₂) is 6.5 to 35.0, preferably ZrO₂ / (Ag₂O+CeO₂) is 8.5 to 20.0, more preferably ZrO₂ / (Ag₂O+CeO₂) is 11.0 to 18.0; and The ratio of (Ag₂O+SnO₂+Sb₂O₃) / CeO₂ is 1.0–30.0, preferably 3.0–20.0, more preferably 5.0–12.5, and even more preferably 7.5–10.0. ; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.0, preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4 to 5.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.7, and even more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.2.

[0062] (56) The photosensitive microcrystalline glass article according to any one of (40) to (55), wherein the components are expressed as weight percentages, wherein: SiO2: 68-77%, preferably SiO2: 69.5-75.5%; and / or R2O+Li2O+Al2O3: 17.5-29.5%, preferably R2O+Li2O+Al2O3: 18.5-26%, more preferably R2O+Li2O+Al2O3: 20-25%; and / or ZrO2: 2-8%, preferably ZrO2: 3-6.5%; and / or CeO2: 0.07-0.4%, preferably CeO2: 0.08-0.4%. 3%; and / or Ag2O: 0.1-0.6%, preferably Ag2O: 0.2-0.5%; and / or Sb2O3+SnO2: 0.1-1%, preferably Sb2O3+SnO2: 0.2-0.7%; and / or Ln2O3: 0-3%, preferably Ln2O3: 0-1%, more preferably without Ln2O3; and / or Fe2O3: 0-0.5%, preferably Fe2O3: 0-0.2%, more preferably without Fe2O3, wherein R2O is one or both of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

[0063] (57) The photosensitive microcrystalline glass article according to any one of (40) to (56), wherein the components are expressed in weight percentage, wherein: R2O: 2-12%, preferably R2O: 3-10%, more preferably R2O: 4-8%; and / or Li2O: 5-15%, preferably Li2O: 7-13%, more preferably Li2O: 8.5-12%; and / or Al2O3: 3-12%, preferably Al2O3: 4-10%, more preferably Al2O3: 5-9%; and / or Sb2O3: 0-1%, preferably Sb2O3: 0.01-0.7%, more preferably Sb2O3: 0.07-0.5%; and / or SnO2: 0-0.5%, preferably SnO2: 0-0.3%, more preferably SnO2: 0-0.2%.

[0064] (58) The photosensitive microcrystalline glass article according to any one of (40) to (57) includes one or more blackened portions and one or more transparent portions; or the photosensitive microcrystalline glass article is entirely blackened.

[0065] (59) The photosensitive microcrystalline glass article according to any one of (40) to (58) wherein the blackened portion contains a crystalline phase and the transparent portion does not contain a crystalline phase.

[0066] (60) The photosensitive microcrystalline glass article according to any one of (40) to (59), wherein the photosensitive microcrystalline glass article contains a lithium silicate crystalline phase, preferably a lithium metasilicate crystalline phase, more preferably the lithium metasilicate crystalline phase in the blackened portion of the photosensitive microcrystalline glass article has a weight percentage of 5 to 50%, further preferably the lithium metasilicate crystalline phase in the blackened portion of the photosensitive microcrystalline glass article has a weight percentage of 5 to 40%, and even more preferably the lithium metasilicate crystalline phase in the blackened portion of the photosensitive microcrystalline glass article has a weight percentage of 10 to 30%.

[0067] (61) The photosensitive microcrystalline glass product according to any one of (40) to (60), the average transmittance T of the transparent portion of the photosensitive microcrystalline glass product with a thickness of 0.2 to 1.5 mm in the 400 to 800 nm wavelength range. 400-800nm The transmittance is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and even more preferably 91.5 to 95.0%; and / or the average transmittance T of the blackened portion of a 0.2 to 1.5 mm thick photosensitive microcrystalline glass article in the 400 to 800 nm wavelength range. 400-800nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass article with a thickness of 0.2 to 1.5 mm at 870 nm is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, even more preferably 1.2% or less, and still more preferably 0.5% or less; and / or the transmittance T of the blackened portion of the photosensitive microcrystalline glass article with a thickness of 0.2 to 1.5 mm. 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass article with a thickness of 0.2 to 1.5 mm at 940 nm is 15.0% or less, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and even more preferably 0.1 to 5.0%; and / or the transmittance T of the blackened portion of the photosensitive microcrystalline glass article with a thickness of 0.2 to 1.5 mm. 940nm The content is 50.0% or less, preferably 0.1% to 35.0%, more preferably 0.3% to 20.0%, even more preferably 0.3% to 15.0%, and even more preferably 0.3% to 10.0%.

[0068] (62) The photosensitive microcrystalline glass product according to any one of (40) to (61) has a thickness of 0.5 to 1.5 mm, preferably 0.8 to 1.2 mm, and more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0069] (63) The photosensitive microcrystalline glass product according to any one of (40) to (62) has a drop ball test height II of 800 mm or more, preferably 900 mm or more, more preferably 1000 mm or more, and even more preferably 1100 mm or more.

[0070] (64) A glass cover containing any of the photosensitive glass described in (1) to (15), and / or any of the photosensitive microcrystalline glass described in (16) to (39), and / or any of the photosensitive microcrystalline glass articles described in (40) to (63).

[0071] (65) Glass components, comprising any of the photosensitive glass described in (1) to (15), and / or any of the photosensitive microcrystalline glass described in (16) to (39), and / or any of the photosensitive microcrystalline glass articles described in (40) to (63).

[0072] (66) An apparatus comprising the photosensitive glass of any one of (1) to (15), and / or the photosensitive microcrystalline glass of any one of (16) to (39), and / or the photosensitive microcrystalline glass article of any one of (40) to (63), and / or the glass cover plate of (64), and / or the glass component of (65).

[0073] (67)(16)~(39) A method for manufacturing photosensitive microcrystalline glass, the method comprising the following steps: forming photosensitive glass, and forming photosensitive microcrystalline glass by crystallization process of photosensitive glass.

[0074] (68) According to the manufacturing method of photosensitive microcrystalline glass described in (67), the crystallization process includes performing a mask exposure treatment on the photosensitive glass, followed by a crystallization heat treatment. The mask exposure treatment includes exposing a specific position or area of ​​the photosensitive glass to ultraviolet light. The ultraviolet light wavelength is preferably 280-360nm, more preferably 300-330nm, and even more preferably 313nm. The exposure time is preferably 5-60 minutes.

[0075] (69) According to the manufacturing method of photosensitive microcrystalline glass according to (67) or (68), the crystallization heat treatment is carried out in two stages, the two-stage crystallization heat treatment includes nucleation process treatment at a first temperature, and then crystal growth process treatment at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490°C to 520°C, the first temperature treatment time is 1 to 4 hours, the second temperature is 540°C to 620°C, and the second temperature treatment time is 1 to 8 hours.

[0076] A method for manufacturing a photosensitive microcrystalline glass product according to any one of (70), (40) to (63), the method comprising the following steps: forming a photosensitive glass, forming a photosensitive microcrystalline glass by a crystallization process, and then forming a photosensitive microcrystalline glass product by a chemical strengthening process.

[0077] (71) The manufacturing method of the photosensitive microcrystalline glass product according to (70) includes a crystallization process of performing a mask exposure treatment on the photosensitive glass and then a crystallization heat treatment. The mask exposure treatment includes ultraviolet exposure of a specific position or area of ​​the photosensitive glass. The ultraviolet wavelength is preferably 280-360nm, more preferably 300-330nm, and even more preferably 313nm. The exposure time is preferably 5-60 minutes.

[0078] (72) According to the manufacturing method of photosensitive microcrystalline glass product as described in (70) or (71), the crystallization heat treatment is carried out in two stages. The two-stage crystallization heat treatment includes nucleation process treatment at a first temperature and crystal growth process treatment at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490°C to 520°C and the first temperature treatment time is 1 to 4 hours. Preferably, the second temperature is 540°C to 620°C and the second temperature treatment time is 1 to 8 hours.

[0079] (73) The method for manufacturing a photosensitive microcrystalline glass article according to any one of (70) to (72), wherein the chemical strengthening process includes immersing the photosensitive microcrystalline glass in a salt bath of molten Na salt, and / or K salt, and / or a mixed Na and K salt at a temperature of 350°C to 470°C for about 1 to 36 hours, preferably at a temperature of 380°C to 460°C, and preferably for a time of 2 to 24 hours.

[0080] The beneficial effects of this invention are: through reasonable component design, the photosensitive glass of this invention has a low coefficient of linear expansion; after photomask exposure and heat treatment, the pattern formed by the obtained photosensitive microcrystalline glass has high precision. The photosensitive microcrystalline glass and photosensitive microcrystalline glass products of this invention have excellent mechanical properties. Detailed Implementation

[0081] The embodiments of the present invention will now be described in detail. However, the present invention is not limited to the embodiments described below, and appropriate modifications can be made to implement it within the scope of the purpose of the present invention. Furthermore, regarding repeated descriptions, although there are appropriate omissions, this will not limit the spirit of the invention.

[0082] The photosensitive glass-ceramic and photosensitive glass-ceramic products of the present invention are materials having a crystalline phase (sometimes also called crystal) and a glassy phase, which are different from amorphous solids. The crystalline phase of the photosensitive glass-ceramic and photosensitive glass-ceramic products can be identified by the peak angle appearing in the X-ray diffraction pattern of X-ray diffraction analysis and / or measured by TEMEDX.

[0083] Through repeated experiments and research, the inventors of this invention have obtained the photosensitive microcrystalline glass or photosensitive microcrystalline glass products of this invention by specifying the content and proportion of the specific components constituting the photosensitive microcrystalline glass and photosensitive microcrystalline glass products to specific values ​​and causing them to precipitate specific crystalline phases.

[0084] In some embodiments, the photosensitive microcrystalline glass of the present invention comprises one or more blackened portions and one or more transparent portions, wherein the transparent portion refers to the average transmittance (T0) of the photosensitive microcrystalline glass in the 400-800nm ​​wavelength range when the photosensitive microcrystalline glass is processed to a thickness of 0.2-1.5mm. 400-800nm The portion with a transmittance of 85.0% or higher, and the blackened portion refers to the average transmittance (T) of the photosensitive microcrystalline glass in the 400–800 nm wavelength range when the photosensitive microcrystalline glass is processed to a thickness of 0.2–1.5 mm. 400-800nm The portion containing less than 5.0% of the photosensitive microcrystalline glass. In some embodiments, the blackened portion of the photosensitive microcrystalline glass contains a crystalline phase, while the transparent portion does not contain a crystalline phase. In some embodiments, the crystalline phase in the blackened portion of the photosensitive microcrystalline glass is uniformly distributed.

[0085] In some embodiments, the photosensitive microcrystalline glass product of the present invention includes one or more blackened portions and one or more transparent portions. The transparent portion refers to the average transmittance (T0) of the photosensitive microcrystalline glass product in the 400-800 nm wavelength range when the product is processed to a thickness of 0.2-1.5 mm. 400-800nm The portion with a transmittance of 85.0% or higher, and the blackened portion refers to the average transmittance (T) of the photosensitive microcrystalline glass product in the 400-800nm ​​wavelength range when the product is processed to a thickness of 0.2-1.5mm. 400-800nm The portion containing less than 5.0% of the photosensitive microcrystalline glass is included. In some embodiments, the blackened portion of the photosensitive microcrystalline glass article contains a crystalline phase, while the transparent portion of the photosensitive microcrystalline glass article does not contain a crystalline phase. In some embodiments, the crystalline phase in the blackened portion of the photosensitive microcrystalline glass article is uniformly distributed.

[0086] In some embodiments, the photosensitive microcrystalline glass or photosensitive microcrystalline glass product of the present invention is entirely blackened, wherein the blackened portion refers to the average transmittance (T0) of the photosensitive microcrystalline glass or photosensitive microcrystalline glass product in the 400-800nm ​​wavelength range when the photosensitive microcrystalline glass or photosensitive microcrystalline glass product is processed to a thickness of 0.2-1.5mm. 400-800nm The portion containing less than 5.0% is included. In some embodiments, the crystalline phase of the blackened portion of the photosensitive microcrystalline glass or photosensitive microcrystalline glass article is uniformly distributed.

[0087] In some embodiments, the photosensitive microcrystalline glass or photosensitive microcrystalline glass product of the present invention is entirely transparent. The transparent portion refers to the average transmittance (T0) of the photosensitive microcrystalline glass or photosensitive microcrystalline glass product in the 400-800nm ​​wavelength range when the photosensitive microcrystalline glass or photosensitive microcrystalline glass product is processed to a thickness of 0.2-1.5mm. 400-800nm The percentage is over 85.0%.

[0088] In some embodiments, the blackened portion of the photosensitive microcrystalline glass or photosensitive microcrystalline glass product of the present invention can form a pattern of any shape and / or size.

[0089] The following describes the range of each component (ingredient) of the photosensitive glass, photosensitive microcrystalline glass, and photosensitive microcrystalline glass products of the present invention. In this specification, unless otherwise specified, the content of each component is expressed as a weight percentage (wt%) relative to the total amount of the photosensitive glass, photosensitive microcrystalline glass, or photosensitive microcrystalline glass product, converted to oxides. Here, "converted to oxides" refers to the total amount of oxides used as raw materials for the photosensitive glass, photosensitive microcrystalline glass, or photosensitive microcrystalline glass products of the present invention, where oxides, composite salts, and hydroxides decompose and transform into oxides upon melting, and the total amount of such oxides is taken as 100%. Furthermore, in this specification, when referred to simply as "glass," it refers to photosensitive glass before crystallization (i.e., crystallization process treatment); after crystallization (i.e., crystallization process treatment), it is referred to as photosensitive microcrystalline glass; and photosensitive microcrystalline glass products refer to products obtained by chemically strengthening photosensitive microcrystalline glass.

[0090] Unless otherwise specified in the specific context, the numerical ranges listed herein include upper and lower limits. "Above" and "below" include endpoint values ​​and all integers and fractions within the range, not limited to the specific values ​​listed when the range is defined. The term "about" as used herein means that formulations, parameters, and other quantities and characteristics are not, and need not be, exact, and may be approximate and / or larger or lower if necessary, reflecting tolerances, conversion factors, and measurement errors, etc. The term "and / or" as used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B.

[0091] In some embodiments of the present invention, the crystalline phase (crystal) in the photosensitive glass-ceramic or photosensitive glass-ceramic product contains a lithium silicate crystalline phase, preferably a lithium metasilicate crystalline phase (Li2SiO3). In some embodiments, the lithium metasilicate crystalline phase has a higher weight percentage than other crystalline phases. In some embodiments, the crystalline phase in the photosensitive glass-ceramic or photosensitive glass-ceramic product comprises only the lithium metasilicate crystalline phase.

[0092] In some embodiments, the weight percentage of lithium metasilicate crystalline phase in the blackened portion of the photosensitive microcrystalline glass or photosensitive microcrystalline glass article is 5-50%, preferably 5-40%, and more preferably 10-30%. In some embodiments, the weight percentage of lithium metasilicate crystalline phase in the blackened portion of the photosensitive microcrystalline glass or photosensitive microcrystalline glass article is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%.

[0093] SiO2 is a glass-forming oxide, forming the framework of glass. It has a low dielectric constant and dielectric loss. SiO2 is a component of lithium metasilicate in photosensitive glass-ceramics. When the SiO2 content is less than 65%, the hardness and coefficient of thermal expansion of the glass decrease, while the dielectric constant and dielectric loss increase. When the SiO2 content is higher than 78%, the transmittance of the blackened portion of the photosensitive glass-ceramic and its products increases. Therefore, the SiO2 content ranges from 65% to 78%, preferably 68% to 77%, and more preferably 69.5% to 75.5%. In some embodiments, it may contain approximately 65%, 65.5%, 66%, 66.5%, 67%, 67.5%, 68%, 68.5%, 69%, 69.5%, 70%, 70.5%, 71%, 71.5%, 72%, 72.5%, 73%, 73.5%, 74%, 74.5%, 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, or 78% SiO2.

[0094] Li₂O is the main component in the formation of crystals in the photosensitive microcrystalline glass and photosensitive microcrystalline glass products of the present invention. When the Li₂O content is less than 5%, the crystal content of the photosensitive microcrystalline glass or photosensitive microcrystalline glass products decreases, and the transmittance of the blackened portion is higher. When the Li₂O content is greater than 15%, the Young's modulus and falling ball test height of the glass decrease, the refractive index and dielectric loss of the glass increase, and the portion of the photosensitive glass not exposed to ultraviolet light during crystallization is prone to crystallization during heat treatment, resulting in a decrease in the transmittance of the transparent portion of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products. Therefore, the Li₂O content is limited to 5-15%, preferably 7-13%, and more preferably 8.5-12%. In some embodiments, it may contain about 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or 15% Li2O.

[0095] The inventors discovered that in some embodiments, the hardness and drop ball test height of the glass increase with increasing SiO2 / Li2O values, while the refractive index decreases with increasing SiO2 / Li2O values. Simultaneously, when SiO2 / Li2O is below 5.5, the transmittance of the transparent portion of the photosensitive glass-ceramic and photosensitive glass-ceramic products decreases, while the transmittance of the blackened portion increases; when SiO2 / Li2O exceeds 10.0, the crystal content of the blackened portion of the photosensitive glass-ceramic and photosensitive glass-ceramic products is low, and the transmittance of the blackened portion increases. Therefore, in some embodiments, a SiO2 / Li2O value of 5.5–10.0 is preferred, a SiO2 / Li2O value of 6.0–9.0 is more preferred, and a SiO2 / Li2O value of 7.0–8.5 is even more preferred. This results in higher transmittance of the transparent portion of the photosensitive glass-ceramic and photosensitive glass-ceramic products in the visible light band, while the transmittance of the blackened portion is lower, making it particularly suitable for optical signal channels or optical shielding systems in electronic products. In some implementations, the SiO2 / Li2O value can be 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, or 10.0.

[0096] Alkali metal oxides (R₂O, which can be one or both of Na₂O and K₂O) can promote the precipitation of lithium metasilicate crystals and improve the transmittance of the blackened portion of photosensitive glass-ceramics and photosensitive glass-ceramic products. When the R₂O content is less than 2%, the crystal content of the photosensitive glass-ceramics and photosensitive glass-ceramic products decreases, the transmittance of the blackened portion increases, and the blackening effect may not even be achieved. When the R₂O content is greater than 12%, the Young's modulus and falling ball test height of the glass decrease, while the refractive index, dielectric constant, and dielectric loss of the glass increase. Therefore, the R₂O content is limited to 2–12%, preferably 3–10%, and more preferably 4–8%. In some implementations, it may contain about 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, or 12% R2O.

[0097] Al2O3 can suppress the decrease in transmittance of the transparent portion of photosensitive glass-ceramics and photosensitive glass-ceramic products after mask exposure and heat treatment, and improve the strength and hardness of the glass, as well as enhance its chemical stability. When the Al2O3 content is less than 3%, the hardness and Young's modulus of the glass decrease, while the coefficient of linear expansion increases. When the Al2O3 content is greater than 12%, the dielectric constant and dielectric loss of the glass increase, the crystal content of the blackened portion of the photosensitive glass-ceramics and photosensitive glass-ceramic products decreases, the transmittance of the blackened portion increases, and the blackening effect may even be impossible to achieve. Therefore, the Al2O3 content is 3-12%, preferably 4-10%, and more preferably 5-9%. In some embodiments, it may contain about 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, or 12% Al2O3.

[0098] In some embodiments, when the total content of R2O, Li2O, and Al2O3 (R2O+Li2O+Al2O3) is less than 15%, the refractive index, hardness, and Young's modulus of the glass decrease; when the content of R2O+Li2O+Al2O3 is greater than 30%, the dielectric constant and dielectric loss of the glass increase. Therefore, it is preferable that the content of R2O+Li2O+Al2O3 is 15-30%, more preferably 17.5-29.5%, even more preferably 18.5-26%, and still more preferably 20-25%. In some embodiments, R2O+Li2O+Al2O3 is approximately 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, or 30%.

[0099] Extensive experimental research by the inventors revealed that, in some embodiments, controlling the ratio (SiO2+Al2O3) / (Li2O+Na2O+K2O) between the total content of SiO2 and Al2O3 (SiO2+Al2O3) and the total content of Li2O, Na2O, and K2O (Li2O+Na2O+K2O) within the range of 3.0 to 7.5 results in lower transmittance of the blackened portion of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products, and a lower refractive index of the glass. This reduces the reflectivity of light signals on the glass surface and increases the incident rate of light signals. Therefore, the preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5, more preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.5, even more preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.0, and even more preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.8. In some implementations, the value of (SiO2+Al2O3) / (Li2O+Na2O+K2O) can be 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5.

[0100] ZrO2 can modulate the precision of the black pattern formation in the blackened areas of glass after mask exposure, improving the interface distinction between the exposed and unexposed areas. This prevents crystallization near the interface in the unexposed areas after heat treatment, thus maintaining high transmittance in the visible light band for the unexposed areas after heat treatment, while ensuring lower transmittance in the blackened areas after heat treatment in the exposed areas. When the ZrO2 content is below 1.5%, the glass's coefficient of thermal expansion increases, making it prone to crystallization in the unexposed areas during heat treatment, leading to reduced transmittance in the transparent areas. When the ZrO2 content is above 10%, the crystal content in photosensitive microcrystalline glass and photosensitive microcrystalline glass products decreases, increasing the transmittance of the blackened areas, and even failing to achieve the desired blackening effect. Therefore, the ZrO2 content is 1.5–10%, preferably 2–8%, and more preferably 3–6.5%. In some embodiments, it may contain about 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10% ZrO2.

[0101] In some embodiments, controlling the total content of K2O and Na2O, specifically the ratio between K2O+Na2O and ZrO2 (K2O+Na2O) / ZrO2, within the range of 0.5 to 7.1, results in higher transmittance of the transparent portion of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products, as well as higher hardness and Young's modulus, and lower dielectric constant. Therefore, a (K2O+Na2O) / ZrO2 ratio of 0.5 to 7.1 is preferred, more preferably 0.7 to 4.5, and even more preferably 0.8 to 2.5. In some implementations, the value of (K2O+Na2O) / ZrO2 can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 6.0, 6.5, 7.0, or 7.1.

[0102] In some embodiments, controlling the ratio of Li2O content to ZrO2 content (Li2O / ZrO2) within the range of 1.0 to 7.5 can result in a glass with a lower refractive index and dielectric loss. This improves the accuracy of the pattern formed within the photosensitive glass-ceramic and photosensitive glass-ceramic products after mask exposure and heat treatment, resulting in higher transmittance in the transparent portions and lower transmittance in the blackened portions. Therefore, a Li2O / ZrO2 ratio of 1.0 to 7.5 is preferred, more preferably 1.2 to 5.0, further preferably 1.4 to 4.3, and even more preferably 1.6 to 3.0. In some implementations, the Li2O / ZrO2 value can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, or 7.5.

[0103] In some embodiments, controlling the total content of SiO2 and Li2O, the ratio between SiO2+Li2O and ZrO2 (SiO2+Li2O) / ZrO2 is within the range of 8.0 to 55.0, which can improve the hardness and drop ball test height of the glass, reduce the coefficient of thermal expansion and dielectric constant of the glass, improve the accuracy of the pattern formed in the photosensitive microcrystalline glass and photosensitive microcrystalline glass products after mask exposure and heat treatment, improve the drop ball test height of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products, and reduce the transmittance of the blackened portion of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products. Therefore, the preferred ratio of (SiO2+Li2O) / ZrO2 is 8.0–55.0, more preferably 10.0–37.0, even more preferably 12.0–25.0, and still more preferably 13.0–20.0. In some embodiments,

[0104] The value of (SiO2+Li2O) / ZrO2 can be 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0. 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0, 30.5, 31.0, 31.5, 32.0, 32.5, 33.0, 33.5, 34.0, 34.5, 35.0, 35.5, 36.0, 36.5, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0, 51.0, 52.0, 53.0, 54.0, 55.0.

[0105] CeO2 acts as a photosensitizer, providing electrons to components such as Ag, Sb, and Sn. When the CeO2 content is below 0.01%, it cannot provide enough electrons, resulting in an excessively low crystal content in the photosensitive glass-ceramic. This reduces the transmittance of the blackened portion of the photosensitive glass-ceramic and its products, and also lowers the Young's modulus. When the CeO2 content is above 0.6%, the transmittance of the transparent portion of the photosensitive glass-ceramic and its products decreases, as does the penetration depth in the ultraviolet band. The internal crystal content of the blackened portion of the photosensitive glass-ceramic and its products decreases, leading to increased transmittance. Therefore, the CeO2 content is 0.01–0.6%, preferably 0.07–0.4%, and more preferably 0.08–0.3%. In some embodiments, it may include approximately 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0 CeO2 concentrations of 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, and 0.6%.

[0106] Ag₂O, as a nucleating agent in the photosensitive microcrystalline glass and photosensitive microcrystalline glass products of this invention, plays a role in improving the blackening effect in the photosensitive microcrystalline glass and photosensitive microcrystalline glass products. When the Ag₂O content is less than 0.01%, the transmittance of the blackened portion of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products increases, or even fails to blacken, and the drop ball test height of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products decreases, the coefficient of thermal expansion increases, and the pattern accuracy decreases. When the Ag₂O content exceeds 0.8%, the transmittance of the transparent portion of the glass decreases during molding or heat treatment, and due to the excessively high nucleating agent content, the number of crystals in the photosensitive microcrystalline glass and photosensitive microcrystalline glass products increases, resulting in excessively fine grain size. The scattering effect of the crystals in the blackened portion on visible light weakens, easily leading to an increase in the transmittance of the blackened portion, and the glass is prone to crystallization during molding. Therefore, the Ag₂O content is limited to 0.01-0.8%, preferably 0.1-0.6%, and more preferably 0.2-0.5%. In some embodiments, it may include approximately 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6%, Ag2O concentrations of 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.7%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, and 0.8%.

[0107] The inventors discovered that, in some embodiments, controlling the Ag2O / CeO2 ratio within the range of 1.0 to 10.0 results in larger grain sizes and higher crystal content in the blackened portion of the photosensitive glass-ceramic and its products. This leads to stronger light scattering in the visible light band, lower transmittance in the blackened portion, and increased hardness and drop ball test height in the photosensitive glass-ceramic and its products. Therefore, an Ag2O / CeO2 ratio of 1.0 to 10.0 is preferred, an Ag2O / CeO2 ratio of 1.5 to 6.5 is more preferred, and an Ag2O / CeO2 ratio of 2.0 to 4.5 is even more preferred. In some implementations, the value of Ag2O / CeO2 can be 1.0, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, or 10.0.

[0108] In some embodiments, controlling the ratio between the ZrO2 content and the total content of Ag2O and CeO2 (Ag2O+CeO2), ZrO2 / (Ag2O+CeO2), within the range of 2.3 to 50.0, can optimize the glass's coefficient of thermal expansion, improve the accuracy of the pattern formed within the photosensitive glass-ceramic after mask exposure and heat treatment, and simultaneously increase the transmittance of the transparent portions of the photosensitive glass-ceramic and photosensitive glass-ceramic products while reducing the transmittance of the blackened portions. It can also improve the hardness and drop height of the glass and photosensitive glass-ceramic products. Therefore, a ZrO2 / (Ag2O+CeO2) ratio of 2.3 to 50.0 is preferred, and a ZrO2 / (Ag2O+CeO2) ratio of more preferred is...

[0109] The ZrO2 / (Ag2O+CeO2) ratio is 6.5 to 35.0, more preferably 8.5 to 20.0, and even more preferably 11.0 to 18.0. In some embodiments, the value of ZrO2 / (Ag2O+CeO2) can be 2.3, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, or 19. 0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0.

[0110] Sb₂O₃ and SnO₂ absorb Ce during ultraviolet exposure. 3+ The released electrons serve to store electrons, providing energy for Ag in subsequent heat treatment processes. + Electrons are provided to form Ag colloid nuclei, promoting the blackening of photosensitive glass-ceramics. When the content of Sb₂O₃+SnO₂ is below 0.05%, the photosensitive glass-ceramics or photosensitive glass-ceramic products are difficult to achieve a blackening effect. When the content of Sb₂O₃+SnO₂ is above 1.2%, the blackened portion of the photosensitive glass-ceramics or photosensitive glass-ceramic products tends to have increased transmittance. Therefore, the content of Sb₂O₃+SnO₂ is 0.05-1.2%, preferably 0.1-1%, and more preferably 0.2-0.7%. In some embodiments, the content of Sb₂O₃ + SnO₂ is approximately 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, 1.05%, 1.1%, 1.15%, and 1.2%.

[0111] SnO2 has a good effect on promoting the blackening of photosensitive microcrystalline glass. However, in some embodiments, when the SnO2 content is higher than 0.5%, the transmittance of the transparent portion of the glass decreases or even becomes devitrified during forming or heat treatment. Therefore, the SnO2 content is limited to 0-0.5%, preferably 0-0.3%, and more preferably 0-0.2%. The Sb2O3 content is limited to 0-1%, preferably 0.01-0.7%, and more preferably 0.07-0.5%. In some embodiments, the content may include approximately 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, and 0.2%. SnO2 concentrations of 4%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, and 0.5%. In some implementations, the content may include approximately 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, etc. 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, and 1% Sb2O3.

[0112] Through extensive experimental research, the inventors discovered that in some embodiments, controlling the total content of Sb₂O₃ and SnO₂, specifically the ratio of Sb₂O₃ + SnO₂ to Ag₂O (Sb₂O₃ + SnO₂) / Ag₂O within the range of 0.1 to 5.0, can reduce the dielectric loss of the glass, increase the drop ball test height of the glass and photosensitive microcrystalline glass products, and result in higher transmittance of the transparent portions and lower transmittance of the blackened portions of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products. Therefore, the preferred method is...

[0113] The ratio of (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, more preferably 0.5 to 3.5, and even more preferably 1.0 to 2.6. In some implementations, the value of (Sb2O3+SnO2) / Ag2O can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, or 5.0.

[0114] In some embodiments, controlling the total content of Ag2O, SnO2, and Sb2O3 (Ag2O+SnO2+Sb2O3) to the content of CeO2 (Ag2O+SnO2+Sb2O3) / CeO2 within the range of 1.0 to 30.0 can result in lower transmittance of the blackened portion of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products, thereby reducing the dielectric constant of the glass while increasing its hardness and Young's modulus. Therefore, it is preferable that (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0 to 30.0, more preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0 to 20.0, even more preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0 to 12.5, and even more preferably...

[0115] The ratio of (Ag₂O + SnO₂ + Sb₂O₃) / CeO₂ is 7.5 to 10.0. In some embodiments, the value of (Ag₂O + SnO₂ + Sb₂O₃) / CeO₂ can be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, or 14.5. 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0, 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0.

[0116] In some embodiments, controlling the total content of Sb2O3, SnO2, and CeO2, the ratio between the content of Sb2O3+SnO2+CeO2 and Ag2O (Sb2O3+SnO2+CeO2) / Ag2O is within the range of 0.1 to 10.0, which can reduce the dielectric loss and expansion coefficient of the glass, resulting in lower transmittance of the blackened portion of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products. Therefore, the preferred ratio of (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.0, more preferably 0.4 to 5.0, even more preferably 0.7 to 3.7, and even more preferably 1.5 to 3.2. In some implementations, the value of (Sb₂O₃+SnO₂+CeO₂) / Ag₂O can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, or 3.4. 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.

[0117] Ln₂O₃ (Ln₂O₃ can be one or more of La₂O₃, Gd₂O₃, and Y₂O₃) can adjust the dielectric constant and dielectric loss of glass, and can be used for Ag… + Providing electrons promotes the blackening of photosensitive glass-ceramics. When Ln2O3 content is higher than 5%, the transmittance of the blackened portion of the photosensitive glass-ceramics and photosensitive glass-ceramic products increases, and the dielectric constant and dielectric loss of the glass increase. Therefore, the Ln2O3 content is limited to 0-5%, preferably 0-3%, more preferably 0-1%, and in some embodiments, it is further preferred to contain no Ln2O3. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, etc. 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, and 5% Ln2O3.

[0118] Fe2O3 can absorb ultraviolet light during ultraviolet exposure of glass, which can then act as a catalyst for Ag. +Providing electrons promotes the blackening of photosensitive glass-ceramics. When the Fe2O3 content is higher than 1%, the transmittance of the transparent portion of the photosensitive glass-ceramics and photosensitive glass-ceramic products decreases in the visible light range, while the transmittance of the blackened portion increases, resulting in a decrease in the drop ball test height of the photosensitive glass-ceramics and photosensitive glass-ceramic products. Therefore, the Fe2O3 content is limited to 0-1%, preferably 0-0.5%, more preferably 0-0.2%, and in some embodiments, it is further preferred that it does not contain Fe2O3. In some implementations, the content may include approximately 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, etc. 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, and 1% Fe2O3.

[0119] The terms "not containing" and "0%" as used herein mean that the compound, molecule, or element was not intentionally added as a raw material to the photosensitive glass, photosensitive microcrystalline glass, or photosensitive microcrystalline glass product of this invention. However, as raw materials and / or equipment used in the production of photosensitive glass, photosensitive microcrystalline glass, or photosensitive microcrystalline glass product, there may be certain unintentionally added impurities or components that may be present in small or trace amounts in the final photosensitive glass, photosensitive microcrystalline glass, or photosensitive microcrystalline glass product. Such cases are also within the scope of protection of this patent.

[0120] The performance indicators of the photosensitive microcrystalline glass and / or photosensitive microcrystalline glass products and / or photosensitive glass of the present invention are tested using the following methods:

[0121] <Light transmittance>

[0122] Light transmittance is tested according to the following method: the sample to be tested is processed to a certain thickness and the opposite surfaces are polished in parallel, and the test is carried out in accordance with the national standard GB / T 7962.12-2010.

[0123] <Coefficient of linear expansion>

[0124] linear expansion coefficient (α)20℃-300℃ Data were obtained from tests conducted at temperatures ranging from 20℃ to 300℃ according to the national standard GB / T7962.16-2010. In this invention, the linear expansion coefficient is sometimes simply referred to as the expansion coefficient.

[0125] <Dielectric constant>

[0126] Dielectric constant (ε) r The test was conducted according to the national standard GB / T 7265.1-1987, and the data was tested under 1GHz conditions.

[0127] <Dielectric Loss>

[0128] Dielectric loss (tanδ) was tested according to the national standard GB / T 7265.1-1987, with data measured under 1GHz conditions.

[0129] <Drop height test>

[0130] A φ20×1mm sample is placed on a glass bearing fixture, and a 32g steel ball is dropped from a specified height. The maximum drop ball test height from which the sample can withstand the impact without breaking is defined as the maximum drop ball test height. Specifically, the test begins at a drop ball test height of 100mm, and the height is increased sequentially to 100mm, 200mm, 300mm, 400mm, 500mm, 600mm, 700mm, 800mm, 900mm, 100mm, 1000mm, 1100mm, 1200mm, and above without breakage. For the embodiment with "Drop Ball Test Height II," a photosensitive microcrystalline glass product is used as the test object. In this embodiment, the test data recorded as 1000mm indicates that the photosensitive microcrystalline glass product withstood the impact without breaking even when a steel ball is dropped from a height of 1000mm. For the embodiment with "Drop Ball Test Height I," photosensitive glass is used as the test object. In this invention, the drop ball test height is sometimes simply referred to as the drop ball height.

[0131] Knoop Hardness

[0132] The load (N) when a diamond pyramidal indenter with a relative face angle of 172.5° is used to press a pyramid-shaped indentation into the test surface, divided by the surface area (mm) calculated from the length of the indentation. 2 The value is represented by ). The test is conducted with a load of 100 (N) and a holding time of 15 (seconds). In this invention, Knoop hardness is sometimes simply referred to as hardness.

[0133] Young's Modulus

[0134] Young's modulus (E) is obtained by ultrasonic testing of its longitudinal and transverse wave velocities, and then calculated using the following formula.

[0135]

[0136] G = V S 2 ρ

[0137] In the formula: E is Young's modulus, Pa;

[0138] G is the shear modulus, Pa;

[0139] V T The transverse wave velocity is in m / s;

[0140] V S The longitudinal wave velocity is given in m / s.

[0141] ρ is the density of glass, in g / cm³ 3 .

[0142] <Refractive index>

[0143] Refractive index (n) d Test according to the method specified in GB / T7962.1-2010.

[0144] The photosensitive glass of this invention has the following properties:

[0145] 1) In some embodiments, the refractive index (n) of the photosensitive glass of the present invention is... d The value is 1.51 to 1.55, preferably 1.52 to 1.54, more preferably 1.53 to 1.535, and even more preferably 1.53112 to 1.53284.

[0146] 2) In some embodiments, the Young's modulus (E) of the photosensitive glass of the present invention is 7000 × 10⁻⁶. 7 Pa ~ 9500 × 10 7 Pa, preferably 7500 × 10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa ~ 9014 × 10 7 Pa, more preferably 8005 × 10 7 Pa~8488×10 7 Pa.

[0147] 3) In some embodiments, the Knoop hardness (Hk) of the photosensitive glass of the present invention 0.1 ) is 450 kgf / mm 2 The above values ​​are preferably 470–600 kgf / mm². 2 More preferably, it is 480–582 kgf / mm 2 More preferably, it is 492–532 kgf / mm2 .

[0148] 4) In some embodiments, the drop ball test height I of the photosensitive glass of the present invention is 200 mm or more, preferably 300 mm or more, and more preferably 400 mm or more.

[0149] 5) In some embodiments, the dielectric loss (tanδ) of the photosensitive glass of the present invention is 11.0 × 10⁻⁶. -3 The preferred value is 7.0×10. -3 ~10.5×10 -3 More preferably 7.2×10 -3 ~9.8×10 -3 Further preferred is 7.4×10 -3 ~9.2×10 -3 .

[0150] 6) In some embodiments, the dielectric constant (ε) of the photosensitive glass of the present invention r The value is 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and even more preferably 6.3 to 7.0.

[0151] 7) In some embodiments, the coefficient of linear expansion (α) of the photosensitive glass of the present invention is... 20℃-300℃ ) is 100×10 -7 Below / ℃, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, further preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0152] The photosensitive microcrystalline glass of this invention has the following properties:

[0153] 1) In some embodiments, the average transmittance (T0.2) of the transparent portion of the 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range is... 400-800nm The content of the saturation is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, even more preferably 91.0% or more, and even more preferably 91.5 to 95.0%. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and even more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0154] 2) In some embodiments, the average transmittance (T) of the blackened portion of the 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range is... 400-800nm The content of the component is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, even more preferably 1.2% or less, and even more preferably 0.5% or less. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and even more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0155] 3) In some embodiments, the transmittance (T) of the blackened portion of the 0.2–1.5 mm thick photosensitive microcrystalline glass at 870 nm is... 870nm The content of the active ingredient is 15.0% or less, preferably 0.1-12.5%, more preferably 0.1-10%, even more preferably 0.1-8.0%, and even more preferably 0.1-5.0%. The thickness is preferably 0.5-1.5 mm, more preferably 0.8-1.2 mm, and even more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0156] 4) In some embodiments, the transmittance (T) of the blackened portion of the 0.2–1.5 mm thick photosensitive microcrystalline glass at 940 nm is... 940nm The content of the component is 50.0% or less, preferably 0.1-35.0%, more preferably 0.3-20.0%, even more preferably 0.3-15.0%, and even more preferably 0.3-10.0%. The thickness is preferably 0.5-1.5 mm, more preferably 0.8-1.2 mm, and even more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0157] In some embodiments, since no crystals are formed in the transparent portion of the photosensitive microcrystalline glass of the present invention, it possesses the same properties as the aforementioned photosensitive glass, such as Young's modulus (E) and Knoop hardness (Hk). 0.1 ), drop ball test height, dielectric loss (tanδ), dielectric constant (ε) r ), linear expansion coefficient (α) 20℃-300℃ Specifically, in some embodiments, the Young's modulus (E) of the transparent portion of the photosensitive microcrystalline glass of the present invention is 7000 × 10⁻⁶. 7 Pa ~ 9500 × 10 7 Pa, preferably 7500 × 10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7Pa ~ 9014 × 10 7 Pa, more preferably 8005 × 10 7 Pa~8488×10 7 Pa. In some embodiments, the Knoop hardness (Hk) of the transparent portion of the photosensitive microcrystalline glass of the present invention... 0.1 ) is 450 kgf / mm 2 The above values ​​are preferably 470–600 kgf / mm². 2 More preferably, it is 480–582 kgf / mm 2 More preferably, it is 492–532 kgf / mm 2 In some embodiments, the drop ball test height of the transparent portion of the photosensitive microcrystalline glass of the present invention is 200 mm or more, preferably 300 mm or more, and more preferably 400 mm or more. In some embodiments, the dielectric loss (tanδ) of the transparent portion of the photosensitive microcrystalline glass of the present invention is 11.0 × 10⁻⁶. -3 The preferred value is 7.0×10. -3 ~10.5×10 -3 More preferably 7.2×10 -3 ~9.8×10 -3 Further preferred is 7.4×10 -3 ~9.2×10 -3 In some embodiments, the dielectric constant (ε) of the transparent portion of the photosensitive microcrystalline glass of the present invention is... r The coefficient of linear expansion (α) of the transparent portion of the photosensitive microcrystalline glass of the present invention is 5.5–8.5, preferably 6.0–8.0, more preferably 6.2–7.7, and even more preferably 6.3–7.0. In some embodiments, the coefficient of linear expansion (α) of the transparent portion of the photosensitive microcrystalline glass of the present invention is... 20℃-300℃ ) is 100×10 -7 Below / ℃, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, further preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0158] The photosensitive microcrystalline glass product of this invention has the following properties:

[0159] 1) In some embodiments, the average transmittance (T) of the transparent portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass article in the 400–800 nm wavelength range. 400-800nmThe content of the saturation is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, even more preferably 91.0% or more, and even more preferably 91.5 to 95.0%. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and even more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0160] 2) In some embodiments, the average transmittance (T) of the blackened portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass product in the 400–800 nm wavelength range is... 400-800nm The content of the component is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, even more preferably 1.2% or less, and even more preferably 0.5% or less. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and even more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0161] 3) In some embodiments, the transmittance (T) of the blackened portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass article at 870 nm is... 870nm The content of the active ingredient is 15.0% or less, preferably 0.1-12.5%, more preferably 0.1-10%, even more preferably 0.1-8.0%, and even more preferably 0.1-5.0%. The thickness is preferably 0.5-1.5 mm, more preferably 0.8-1.2 mm, and even more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0162] 4) In some embodiments, the transmittance (T) of the blackened portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass article at 940 nm is... 940nm The content of the component is 50.0% or less, preferably 0.1-35.0%, more preferably 0.3-20.0%, even more preferably 0.3-15.0%, and even more preferably 0.3-10.0%. The thickness is preferably 0.5-1.5 mm, more preferably 0.8-1.2 mm, and even more preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, or 1.2 mm.

[0163] 5) In some embodiments, the drop ball test height II of the photosensitive microcrystalline glass product of the present invention is 800 mm or more, preferably 900 mm or more, more preferably 1000 mm or more, and even more preferably 1100 mm or more.

[0164] In some embodiments, the photosensitive glass / photosensitive microcrystalline glass / photosensitive microcrystalline glass products of the present invention have a low dielectric constant and dielectric loss, which can reduce the transmission loss of electrical signals.

[0165] In some embodiments, the photosensitive glass / photosensitive microcrystalline glass / photosensitive microcrystalline glass products of the present invention have high Knoop hardness, Young's modulus, and drop height.

[0166] In some embodiments, the photosensitive glass / photosensitive microcrystalline glass / photosensitive microcrystalline glass articles of the present invention have a low coefficient of linear expansion to improve the accuracy of the optical signal channel or mask pattern.

[0167] In some embodiments, the photosensitive glass / photosensitive microcrystalline glass / photosensitive microcrystalline glass products of the present invention have a low refractive index, which can reduce the reflectivity of surface light signals and increase the incident rate of light signals.

[0168] Due to the aforementioned superior properties, the photosensitive microcrystalline glass, photosensitive microcrystalline glass products, and photosensitive glass of the present invention can be widely used to manufacture glass covers or glass components. Furthermore, the photosensitive microcrystalline glass, photosensitive microcrystalline glass products, photosensitive glass, and glass covers or glass components made therefrom can be applied to the manufacture of various instruments or equipment, including but not limited to electronic devices, medical devices, decorations, or handicrafts, such as mobile phones, watches, computers, and biomedical testing equipment. These can be used to manufacture partial light-shielding glass or patterned cover glass for mobile phones, smartphones, tablets, laptops, televisions, etc., or for optical signal channel glass in smartwatches, biomedical devices, etc., or for manufacturing patterned decorative or handicraft glass.

[0169] The photosensitive glass, photosensitive microcrystalline glass, and photosensitive microcrystalline glass products of the present invention can be produced and manufactured by the following methods:

[0170] The manufacturing method of photosensitive glass includes the following steps: weighing raw materials according to the component ratio and mixing them evenly; placing the evenly mixed raw materials into a platinum or quartz crucible; melting, clarifying, and homogenizing at 1450-1600℃; cooling the mixture; pouring the molten glass into a mold to form the glass; and circulating cooling air to ensure that the glass does not crystallize. Preferably, the mold is preheated to 200-500℃. The formed glass and the mold are placed together in an annealing furnace for heat preservation and annealing. Then, the power is turned off and the glass is cooled with the furnace to obtain photosensitive glass.

[0171] The manufacturing method of photosensitive microcrystalline glass includes the following steps: forming photosensitive glass, processing the photosensitive glass through a crystallization process, or processing the photosensitive glass into a glass element of a specific shape and then processing it through a crystallization process to obtain the photosensitive microcrystalline glass of the present invention. The method of processing the glass element of a specific shape according to the present invention includes methods known to those skilled in the art, such as hot pressing, grinding, or polishing. The crystallization process of the present invention includes mask exposure of the photosensitive glass, followed by crystallization heat treatment, to uniformly precipitate crystals at the exposed locations on the glass. The mask exposure process of the present invention refers to ultraviolet exposure at specific locations or areas of the photosensitive glass. The ultraviolet wavelength is preferably 280–360 nm, more preferably 300–330 nm, and even more preferably 313 nm. A dedicated photomask pattern can be customized according to application needs. The exposure time is preferably 5–60 minutes. The crystallization heat treatment of the present invention can be carried out in one stage or in two stages, preferably in two stages. The two-stage crystallization heat treatment refers to performing a nucleation process at a first temperature and then performing a crystal growth process at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490℃~520℃ and the first temperature treatment time is 1~4 hours. Preferably, the second temperature is 540℃~620℃ and the second temperature treatment time is 1~8 hours.

[0172] The manufacturing method of photosensitive microcrystalline glass products includes the following steps: processing the photosensitive microcrystalline glass of the present invention through a chemical strengthening process, or processing the photosensitive microcrystalline glass into a photosensitive microcrystalline glass element of a specific shape and then processing it through a chemical strengthening process to obtain the photosensitive microcrystalline glass product of the present invention. The methods for processing the present invention into a specific shape include methods known to those skilled in the art, such as hot pressing, grinding, or polishing.

[0173] The chemical strengthening method described in this invention is ion exchange. During ion exchange, smaller metal ions in the photosensitive glass-ceramic are replaced or "exchanged" by larger metal ions with the same valence state located nearby. This replacement of smaller ions with larger ions creates compressive stress within the photosensitive glass-ceramic, forming a compressive stress layer.

[0174] In some embodiments, the metal ion is a monovalent alkali metal ion (e.g., Na+). + K + 、Rb + Cs + (etc.), ion exchange is carried out by immersing the photosensitive microcrystalline glass in a salt bath containing at least one molten salt containing larger metal ions, which replace smaller metal ions in the photosensitive microcrystalline glass. Alternatively, other monovalent metal ions such as Ag + 、Tl + Cu +Ion exchange processes can also be used to exchange monovalent ions. One or more ion exchange processes used to chemically strengthen photosensitive glass-ceramics may include, but are not limited to, immersing the glass in a single salt bath, or immersing it in multiple salt baths having the same or different compositions, with washing and / or annealing steps added between immersions.

[0175] In some embodiments, the photosensitive microcrystalline glass can be ion-exchanged by immersing it in a salt bath of molten Na salt (such as NaNO3) and / or K salt (such as KNO3) and / or a mixed Na and K salt at a temperature of about 350°C to 470°C for 1 to 36 hours, preferably at a temperature range of 380°C to 460°C and for a time range of 2 to 24 hours.

[0176] In some embodiments, the photosensitive glass of the present invention can be manufactured into reinforced glass through the above-described chemical strengthening process, and then processed into photosensitive microcrystalline glass products through the above-described crystallization process. In some embodiments, the photosensitive glass of the present invention can be processed into glass elements, and then the glass elements can be manufactured into reinforced glass through the above-described chemical strengthening process, and then processed into photosensitive microcrystalline glass products through the above-described crystallization process.

[0177] Example

[0178] To further clarify and illustrate the technical solution of the present invention, the following non-limiting embodiments are provided. While the embodiments of the present invention have made considerable efforts to ensure the accuracy of numerical values ​​(e.g., quantities), some errors and deviations must be taken into account. The composition itself is based on oxides and is given in weight percent, and has been normalized to 100%.

[0179] <Example of Photosensitive Glass>

[0180] In this embodiment, photosensitive glass with the compositions shown in Tables 1 to 4 was obtained using the above-described manufacturing method. Furthermore, the characteristics of each photosensitive glass were measured using the testing method described in this invention, and the measurement results are shown in Tables 1 to 4.

[0181] Table 1.

[0182]

[0183]

[0184] Table 2.

[0185]

[0186]

[0187] Table 3.

[0188]

[0189]

[0190] Table 4.

[0191]

[0192]

[0193] <Example of Photosensitive Microcrystalline Glass>

[0194] In this embodiment, photosensitive microcrystalline glass with the compositions shown in Tables 5 to 8 was obtained using the above-described manufacturing method. Furthermore, the characteristics of each photosensitive microcrystalline glass were measured using the testing method described in this invention, and the measurement results are shown in Tables 5 to 8. In the following embodiments, the transmittance of the photosensitive microcrystalline glass was tested using a 1 mm thick sample.

[0195] Table 5.

[0196]

[0197]

[0198] Table 6.

[0199]

[0200]

[0201] Table 7.

[0202]

[0203]

[0204] Table 8.

[0205]

[0206]

[0207] <Examples of Photosensitive Microcrystalline Glass Products>

[0208] In this embodiment, photosensitive microcrystalline glass products with the compositions shown in Tables 9 to 12 were obtained using the manufacturing method described above. Furthermore, the characteristics of each photosensitive microcrystalline glass product were measured using the testing method described in this invention, and the measurement results are shown in Tables 9 to 12. In the following embodiments, the transmittance of the photosensitive microcrystalline glass products was tested using a 1 mm thick sample.

[0209] Table 9.

[0210]

[0211]

[0212] Table 10.

[0213]

[0214]

[0215] Table 11.

[0216]

[0217]

[0218] Table 12.

[0219]

[0220]

Claims

1. A photosensitive glass, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 65–74%; ZrO2: 1.5–10%; R2O+Li2O+Al2O3: 21.5–30%; CeO2: 0.01–0.6%; Ag2O: 0.01–0.8%; Sb2O3+SnO2: 0.05–1.2%, wherein ZrO2 / (Ag2O+CeO2) is 6.5–50.0, (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0–14.0, (SiO2+Li2O) / ZrO2 is 8.0–55.0, and the R2O is one or both of Na2O and K2O.

2. The photosensitive glass according to claim 1, characterized in that, Its components, expressed as a percentage by weight, also contain: Ln2O3: 0–5%; and / or Fe2O3: 0–1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

3. Photosensitive glass, characterized in that, Its composition contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2, and Ag2O, expressed as a weight percentage: SiO2: 65–74%, R2O+Li2O+Al2O3: 21.5–30%, (SiO2+Li2O) / ZrO2: 8.0–55.0, ZrO2 / (Ag2O+CeO2): 6.5–50.0, (Ag2O+SnO2+Sb2O3) / CeO2: 1.0–14.

0. The R2O is one or both of Na2O and K2O. The coefficient of linear expansion α of the photosensitive glass is... 20℃-300℃ 100×10 -7 / ℃ below.

4. The photosensitive glass according to claim 3, characterized in that, Its components, expressed as a percentage by weight, contain: ZrO2: 1.5–10%; CeO2: 0.01–0.6%; Ag2O: 0.01–0.8%; Sb2O3+SnO2: 0.05–1.2%; Ln2O3: 0–5%; Fe2O3: 0–1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

5. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 5.5 to 10.0; and / or (K2O+Na2O) / ZrO2 is 0.5 to 7.1; and / or Li2O / ZrO2 is 1.0 to 7.5; and / or (SiO2+Li2O) / ZrO2 is 10.0 to 37.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.

5.

6. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 6.0 to 9.0; and / or (K2O+Na2O) / ZrO2 is 0.7 to 4.5; and / or Li2O / ZrO2 is 1.2 to 5.0; and / or (SiO2+Li2O) / ZrO2 is 12.0 to 25.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.

5.

7. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 7.0 to 8.5; and / or (K2O+Na2O) / ZrO2 is 0.8 to 2.5; and / or Li2O / ZrO2 is 1.4 to 4.3; and / or (SiO2+Li2O) / ZrO2 is 13.0 to 20.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.

0.

8. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, of which: Li2O / ZrO2 is 1.6 to 3.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.

8.

9. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0; and / or Ag2O / CeO2 is 1.0 to 10.0; and / or ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0 to 14.0; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.

0.

10. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 0.5-3.5; and / or Ag2O / CeO2 is 1.5-6.5; and / or ZrO2 / (Ag2O+CeO2) is 8.5-20.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0-12.5; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.4-5.

0.

11. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; and / or Ag2O / CeO2 is 2.0 to 4.5; and / or ZrO2 / (Ag2O+CeO2) is 11.0 to 18.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 7.5 to 10.0; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.

7.

12. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, of which (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.

2.

13. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2: 68-74%; and / or R2O+Li2O+Al2O3: 21.5-29.5%; and / or ZrO2: 2-8%; and / or CeO2: 0.07-0.4%; and / or Ag2O: 0.1-0.6%; and / or Sb2O3+SnO2: 0.1-1%; and / or Ln2O3: 0-3%; and / or Fe2O3: 0-0.5%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

14. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2: 69.5-74%; and / or R2O+Li2O+Al2O3: 21.5-26%; and / or ZrO2: 3-6.5%; and / or CeO2: 0.08-0.3%; and / or Ag2O: 0.2-0.5%; and / or Sb2O3+SnO2: 0.2-0.7%; and / or Ln2O3: 0-1%; and / or Fe2O3: 0-0.2%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

15. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: R2O+Li2O+Al2O3: 21.5~25%; and / or does not contain Ln2O3; and / or does not contain Fe2O3, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

16. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 2-12%; and / or Li2O: 5-15%; and / or Al2O3: 3-12%; and / or Sb2O3: 0-1%; and / or SnO2: 0-0.5%.

17. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 3-10%; and / or Li2O: 7-13%; and / or Al2O3: 4-10%; and / or Sb2O3: 0.01-0.7%; and / or SnO2: 0-0.3%.

18. The photosensitive glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 4-8%; and / or Li2O: 8.5-12%; and / or Al2O3: 5-9%; and / or Sb2O3: 0.07-0.5%; and / or SnO2: 0-0.2%.

19. The photosensitive glass according to any one of claims 1 to 4, characterized in that, The refractive index n of the photosensitive glass d It is 1.51 to 1.55; and / or Young's modulus E is 7000 × 10⁻⁶. 7 Pa ~ 9500 × 10 7 Pa; and / or Knoop hardness Hk 0.1 450 kgf / mm 2 The above; and / or the drop ball test height I is 200 mm or more; and / or the dielectric loss tanδ is 11.0 × 10⁻⁶. -3 The following; and / or dielectric constant ε r The coefficient of linear expansion is 5.5 to 8.5; and / or the coefficient of linear expansion α. 20℃-300℃ 100×10 -7 / ℃ below.

20. The photosensitive glass according to any one of claims 1 to 4, characterized in that, The refractive index n of the photosensitive glass d It is 1.52 to 1.54; and / or Young's modulus E is 7500 × 10⁻⁶. 7 Pa~9200×10 7 Pa; and / or Knoop hardness Hk 0.1 470–600 kgf / mm 2 ; and / or the drop ball test height I is 300 mm or more; and / or the dielectric loss tanδ is 7.0 × 10⁻⁶. -3 ~10.5×10 -3 ; and / or dielectric constant ε r The coefficient of linear expansion is 6.0 to 8.0; and / or the coefficient of linear expansion α. 20℃-300℃ 65×10 -7 / ℃~100×10 -7 / ℃.

21. The photosensitive glass according to any one of claims 1 to 4, characterized in that, The refractive index n of the photosensitive glass d It is 1.53 to 1.535; and / or Young's modulus E is 7836 × 10⁻⁶. 7 Pa ~ 9014 × 10 7 Pa; and / or Knoop hardness Hk 0.1 480–582 kgf / mm 2 ; and / or the drop ball test height I is 400 mm or more; and / or the dielectric loss tanδ is 7.2 × 10⁻⁶. -3 ~9.8×10 -3 ; and / or dielectric constant ε r The coefficient of linear expansion is 6.2 to 7.7; and / or the coefficient of linear expansion α. 20℃-300℃ 71×10 -7 / ℃~95×10 -7 / ℃.

22. The photosensitive glass according to any one of claims 1 to 4, characterized in that, The refractive index n of the photosensitive glass d It is 1.53112 to 1.53284; and / or Young's modulus E is 8005 × 10⁻⁶. 7 Pa~8488×10 7 Pa; and / or Knoop hardness Hk 0.1 492–532 kgf / mm 2 ; and / or dielectric loss tanδ is 7.4 × 10⁻⁶ -3 ~9.2×10 -3 ; and / or dielectric constant ε r The coefficient of linear expansion is 6.3 to 7.0; and / or the coefficient of linear expansion α. 20℃-300℃ 75×10 -7 / ℃~90×10 -7 / ℃.

23. A photosensitive microcrystalline glass, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 65–74%; ZrO2: 1.5–10%; R2O+Li2O+Al2O3: 21.5–30%; CeO2: 0.01–0.6%; Ag2O: 0.01–0.8%; Sb2O3+SnO2: The content is 0.05-1.2%, wherein ZrO2 / (Ag2O+CeO2) is 6.5-50.0, (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0-14.0, and (SiO2+Li2O) / ZrO2 is 8.0-55.

0. The R2O is one or two of Na2O and K2O, and the photosensitive microcrystalline glass contains a lithium silicate crystalline phase.

24. The photosensitive microcrystalline glass according to claim 23, characterized in that, Its components, expressed as a percentage by weight, also contain: Ln2O3: 0–5%; and / or Fe2O3: 0–1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

25. A photosensitive microcrystalline glass, characterized in that, Its composition contains SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, and its composition is expressed as a weight percentage, wherein SiO2: 65-74%, R2O+Li2O+Al2O3: 21.5-30%, ZrO2 / (Ag2O+CeO2) is 6.5-50.0, (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0-14.0, (SiO2+Li2O) / ZrO2 is 8.0-55.0, and the R2O is one or two of Na2O and K2O, and the photosensitive microcrystalline glass contains a lithium silicate crystalline phase.

26. The photosensitive microcrystalline glass according to claim 25, characterized in that, Its components, expressed as a percentage by weight, contain: ZrO2: 1.5–10%; CeO2: 0.01–0.6%; Ag2O: 0.01–0.8%; Sb2O3+SnO2: 0.05–1.2%; Ln2O3: 0–5%; Fe2O3: 0–1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

27. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 5.5 to 10.0; and / or (K2O+Na2O) / ZrO2 is 0.5 to 7.1; and / or Li2O / ZrO2 is 1.0 to 7.5; and / or (SiO2+Li2O) / ZrO2 is 10.0 to 37.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.

5.

28. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 6.0 to 9.0; and / or (K2O+Na2O) / ZrO2 is 0.7 to 4.5; and / or Li2O / ZrO2 is 1.2 to 5.0; and / or (SiO2+Li2O) / ZrO2 is 12.0 to 25.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.

5.

29. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 7.0 to 8.5; and / or (K2O+Na2O) / ZrO2 is 0.8 to 2.5; and / or Li2O / ZrO2 is 1.4 to 4.3; and / or (SiO2+Li2O) / ZrO2 is 13.0 to 20.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.

0.

30. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a weight percentage, of which: Li2O / ZrO2 is 1.6 to 3.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.

8.

31. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0; and / or Ag2O / CeO2 is 1.0 to 10.0; and / or ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0 to 14.0; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.

0.

32. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 0.5-3.5; and / or Ag2O / CeO2 is 1.5-6.5; and / or ZrO2 / (Ag2O+CeO2) is 8.5-20.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0-12.5; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.4-5.

0.

33. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; and / or Ag2O / CeO2 is 2.0 to 4.5; and / or ZrO2 / (Ag2O+CeO2) is 11.0 to 18.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 7.5 to 10.0; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.

7.

34. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a weight percentage, of which (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.

2.

35. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2: 68-74%; and / or R2O+Li2O+Al2O3: 21.5-29.5%; and / or ZrO2: 2-8%; and / or CeO2: 0.07-0.4%; and / or Ag2O: 0.1-0.6%; and / or Sb2O3+SnO2: 0.1-1%; and / or Ln2O3: 0-3%; and / or Fe2O3: 0-0.5%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

36. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2: 69.5-74%; and / or R2O+Li2O+Al2O3: 21.5-26%; and / or ZrO2: 3-6.5%; and / or CeO2: 0.08-0.3%; and / or Ag2O: 0.2-0.5%; and / or Sb2O3+SnO2: 0.2-0.7%; and / or Ln2O3: 0-1%; and / or Fe2O3: 0-0.2%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

37. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a weight percentage, wherein: R2O+Li2O+Al2O3: 21.5~25%; and / or does not contain Ln2O3; and / or does not contain Fe2O3, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

38. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 2-12%; and / or Li2O: 5-15%; and / or Al2O3: 3-12%; and / or Sb2O3: 0-1%; and / or SnO2: 0-0.5%.

39. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 3-10%; and / or Li2O: 7-13%; and / or Al2O3: 4-10%; and / or Sb2O3: 0.01-0.7%; and / or SnO2: 0-0.3%.

40. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 4-8%; and / or Li2O: 8.5-12%; and / or Al2O3: 5-9%; and / or Sb2O3: 0.07-0.5%; and / or SnO2: 0-0.2%.

41. The photosensitive microcrystalline glass according to any one of claims 23 to 26, characterized in that, The photosensitive microcrystalline glass comprises one or more blackened portions and one or more transparent portions; or the entire photosensitive microcrystalline glass is blackened.

42. The photosensitive microcrystalline glass according to claim 41, characterized in that, The blackened portion contains a crystalline phase, while the transparent portion does not contain a crystalline phase.

43. The photosensitive microcrystalline glass according to claim 41, characterized in that, The photosensitive microcrystalline glass contains a lithium metasilicate crystalline phase.

44. The photosensitive microcrystalline glass according to claim 41, characterized in that, In the blackened portion of the photosensitive microcrystalline glass, the weight percentage of the lithium metasilicate crystalline phase is 5-50%.

45. The photosensitive microcrystalline glass according to claim 41, characterized in that, In the blackened portion of the photosensitive microcrystalline glass, the weight percentage of the lithium metasilicate crystalline phase is 5-40%.

46. ​​The photosensitive microcrystalline glass according to claim 41, characterized in that, In the blackened portion of the photosensitive microcrystalline glass, the weight percentage of the lithium metasilicate crystalline phase is 10-30%.

47. The photosensitive microcrystalline glass according to claim 41, characterized in that, The average transmittance T of the transparent portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range. 400-800nm The average transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range is above 85.0%. 400-800nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm at 870 nm is less than 5.0%. 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm at 940 nm is less than 15.0%; 940nm It is below 50.0%.

48. The photosensitive microcrystalline glass according to claim 41, characterized in that, The average transmittance T of the transparent portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range. 400-800nm The transmittance is above 88.0%; and / or the average transmittance T of the blackened portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range. 400-800nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm at 870 nm is less than 3.0%; 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.1–12.5% ​​at 940 nm is 0.1–12.5%; and / or 0.2–1.5 mm thick. 940nm The range is 0.1% to 35.0%.

49. The photosensitive microcrystalline glass according to claim 41, characterized in that, The average transmittance T of the transparent portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range. 400-800nm The average transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range is above 90.0%. 400-800nm The transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm at 870 nm is less than 1.5%. 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.1–10% at 940 nm is 0.1–10%; and / or 0.2–1.5 mm. 940nm The range is 0.3% to 20.0%.

50. The photosensitive microcrystalline glass according to claim 41, characterized in that, The average transmittance T of the transparent portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range. 400-800nm The transmittance is above 91.0%; and / or the average transmittance T of the blackened portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range. 400-800nm The transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm at 870 nm is less than 1.2%; 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.1–8.0% at 940 nm is 0.1–8.0%; and / or 0.2–1.5 mm. 940nm The range is 0.3% to 15.0%.

51. The photosensitive microcrystalline glass according to claim 41, characterized in that, The average transmittance T of the transparent portion of a 0.2–1.5 mm thick photosensitive microcrystalline glass in the 400–800 nm wavelength range. 400-800nm The average transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range is 91.5–95.0%. 400-800nm The transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2–1.5 mm at 870 nm is less than 0.5%. 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass with a thickness of 0.1–5.0% at 940 nm is 0.1–5.0%; and / or 0.2–1.5 mm. 940nm The range is 0.3% to 10.0%.

52. The photosensitive microcrystalline glass according to claim 47, characterized in that, The thickness of the photosensitive microcrystalline glass is 0.5 to 1.5 mm.

53. The photosensitive microcrystalline glass according to claim 47, characterized in that, The thickness of the photosensitive microcrystalline glass is 0.8–1.2 mm.

54. The photosensitive microcrystalline glass according to claim 47, characterized in that, The thickness of the photosensitive microcrystalline glass is 0.5mm, 0.7mm, 0.8mm, 0.9mm, 1.0mm, 1.1mm, and 1.2mm.

55. A photosensitive microcrystalline glass product, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 65–74%; ZrO2: 1.5–10%; R2O+Li2O+Al2O3: 21.5–30%; CeO2: 0.01–0.6%; Ag2O: 0.01–0.8%; Sb2O3+SnO2: The content is 0.05-1.2%, wherein ZrO2 / (Ag2O+CeO2) is 6.5-50.0, (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0-14.0, and (SiO2+Li2O) / ZrO2 is 8.0-55.

0. The R2O is one or two of Na2O and K2O, and the photosensitive microcrystalline glass product contains lithium silicate crystalline phase.

56. The photosensitive microcrystalline glass product according to claim 55, characterized in that, Its components, expressed as a percentage by weight, also contain: Ln2O3: 0–5%; and / or Fe2O3: 0–1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

57. A photosensitive microcrystalline glass product, characterized in that, Its components include SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2, and Ag2O. The components are expressed as weight percentages, wherein SiO2: 65-74%, R2O+Li2O+Al2O3: 21.5-30%, ZrO2 / (Ag2O+CeO2) is 6.5-50.0, (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0-14.0, and (SiO2+Li2O) / ZrO2 is 8.0-55.

0. The R2O is one or both of Na2O and K2O. The photosensitive microcrystalline glass product contains a lithium silicate crystalline phase.

58. The photosensitive microcrystalline glass product according to claim 57, characterized in that, Its components, expressed as a percentage by weight, contain: ZrO2: 1.5–10%; and / or CeO2: 0.01–0.6%; and / or Ag2O: 0.01–0.8%; and / or Sb2O3+SnO2: 0.05–1.2%; and / or Ln2O3: 0–5%; and / or Fe2O3: 0–1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

59. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 5.5 to 10.0; and / or (K2O+Na2O) / ZrO2 is 0.5 to 7.1; and / or Li2O / ZrO2 is 1.0 to 7.5; and / or (SiO2+Li2O) / ZrO2 is 10.0 to 37.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.

5.

60. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 6.0 to 9.0; and / or (K2O+Na2O) / ZrO2 is 0.7 to 4.5; and / or Li2O / ZrO2 is 1.2 to 5.0; and / or (SiO2+Li2O) / ZrO2 is 12.0 to 25.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.

5.

61. The photosensitive microcrystalline glass product according to any one of claims 55 to 58, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Li2O is 7.0 to 8.5; and / or (K2O+Na2O) / ZrO2 is 0.8 to 2.5; and / or Li2O / ZrO2 is 1.4 to 4.3; and / or (SiO2+Li2O) / ZrO2 is 13.0 to 20.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.

0.

62. The photosensitive microcrystalline glass product according to any one of claims 55 to 58, characterized in that, Its components are expressed as a weight percentage, of which: Li2O / ZrO2 is 1.6 to 3.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.

8.

63. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0; and / or Ag2O / CeO2 is 1.0 to 10.0; and / or ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0 to 14.0; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.

0.

64. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 0.5-3.5; and / or Ag2O / CeO2 is 1.5-6.5; and / or ZrO2 / (Ag2O+CeO2) is 8.5-20.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0-12.5; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.4-5.

0.

65. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as weight percentages, wherein: (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; and / or Ag2O / CeO2 is 2.0 to 4.5; and / or ZrO2 / (Ag2O+CeO2) is 11.0 to 18.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 7.5 to 10.0; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.

7.

66. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a weight percentage, of which (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.

2.

67. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2: 68-74%; and / or R2O+Li2O+Al2O3: 21.5-29.5%; and / or ZrO2: 2-8%; and / or CeO2: 0.07-0.4%; and / or Ag2O: 0.1-0.6%; and / or Sb2O3+SnO2: 0.1-1%; and / or Ln2O3: 0-3%; and / or Fe2O3: 0-0.5%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

68. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2: 69.5-74%; and / or R2O+Li2O+Al2O3: 21.5-26%; and / or ZrO2: 3-6.5%; and / or CeO2: 0.08-0.3%; and / or Ag2O: 0.2-0.5%; and / or Sb2O3+SnO2: 0.2-0.7%; and / or Ln2O3: 0-1%; and / or Fe2O3: 0-0.2%, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

69. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a weight percentage, wherein: R2O+Li2O+Al2O3: 21.5~25%; and / or does not contain Ln2O3; and / or does not contain Fe2O3, wherein R2O is one or two of Na2O and K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

70. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 2-12%; and / or Li2O: 5-15%; and / or Al2O3: 3-12%; and / or Sb2O3: 0-1%; and / or SnO2: 0-0.5%.

71. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 3-10%; and / or Li2O: 7-13%; and / or Al2O3: 4-10%; and / or Sb2O3: 0.01-0.7%; and / or SnO2: 0-0.3%.

72. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, Its components are expressed as a percentage by weight, wherein: R2O: 4-8%; and / or Li2O: 8.5-12%; and / or Al2O3: 5-9%; and / or Sb2O3: 0.07-0.5%; and / or SnO2: 0-0.2%.

73. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, The photosensitive microcrystalline glass product comprises one or more blackened portions and one or more transparent portions; or the entire photosensitive microcrystalline glass product is blackened.

74. The photosensitive microcrystalline glass product according to claim 73, characterized in that, The blackened portion contains a crystalline phase, while the transparent portion does not contain a crystalline phase.

75. The photosensitive microcrystalline glass product according to claim 73, characterized in that, The photosensitive microcrystalline glass product contains a lithium metasilicate crystalline phase.

76. The photosensitive microcrystalline glass product according to claim 73, characterized in that, In the blackened portion of photosensitive microcrystalline glass products, the weight percentage of lithium metasilicate crystalline phase is 5-50%.

77. The photosensitive microcrystalline glass product according to claim 73, characterized in that, In the blackened portion of photosensitive microcrystalline glass products, the weight percentage of lithium metasilicate crystalline phase is 5-40%.

78. The photosensitive microcrystalline glass product according to claim 73, characterized in that, In the blackened portion of photosensitive microcrystalline glass products, the weight percentage of lithium metasilicate crystalline phase is 10-30%.

79. The photosensitive microcrystalline glass product according to claim 73, characterized in that, The average transmittance T of the transparent portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range. 400-800nm The average transmittance T of the blackened portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range is above 85.0%. 400-800nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass product with a thickness of 0.2–1.5 mm at 870 nm is less than 5.0%. 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass article with a thickness of 0.2–1.5 mm is less than 15.0%; 940nm It is below 50.0%.

80. The photosensitive microcrystalline glass product according to claim 73, characterized in that, The average transmittance T of the transparent portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range. 400-800nm The average transmittance T of the blackened portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range is above 88.0%. 400-800nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass product with a thickness of 0.2–1.5 mm at 870 nm is less than 3.0%. 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass product with a thickness of 0.1–12.5% ​​at 940 nm is 0.1–12.5%. 940nm The range is 0.1% to 35.0%.

81. The photosensitive microcrystalline glass product according to claim 73, characterized in that, The average transmittance T of the transparent portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range. 400-800nm The average transmittance T of the blackened portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range is above 90.0%. 400-800nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass product with a thickness of 0.2–1.5 mm at 870 nm is less than 1.5%. 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass product with a thickness of 0.1–10% at 940 nm is 0.1–10%; and / or 0.2–1.5 mm. 940nm The range is 0.3% to 20.0%.

82. The photosensitive microcrystalline glass product according to claim 73, characterized in that, The average transmittance T of the transparent portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range. 400-800nm The average transmittance T of the blackened portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range is above 91.0%. 400-800nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass article with a thickness of 0.2–1.5 mm at 870 nm is less than 1.2%; 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass product with a thickness of 0.1–8.0% and / or 0.2–1.5 mm at 940 nm is [not specified]. 940nm The range is 0.3% to 15.0%.

83. The photosensitive microcrystalline glass product according to claim 73, characterized in that, The average transmittance T of the transparent portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range. 400-800nm The average transmittance T of the blackened portion of photosensitive microcrystalline glass products with a thickness of 0.2–1.5 mm in the 400–800 nm wavelength range is 91.5–95.0%. 400-800nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass product with a thickness of 0.2–1.5 mm at 870 nm is less than 0.5%. 870nm The transmittance T of the blackened portion of a photosensitive microcrystalline glass product with a thickness of 0.1–5.0% at 940 nm is 0.1–5.0%; and / or 0.2–1.5 mm. 940nm The range is 0.3% to 10.0%.

84. The photosensitive microcrystalline glass product according to claim 79, characterized in that, The thickness of the photosensitive microcrystalline glass product is 0.5 to 1.5 mm.

85. The photosensitive microcrystalline glass product according to claim 79, characterized in that, The thickness of the photosensitive microcrystalline glass product is 0.8 to 1.2 mm.

86. The photosensitive microcrystalline glass product according to claim 79, characterized in that, The thickness of the photosensitive microcrystalline glass product is 0.5mm, 0.7mm, 0.8mm, 0.9mm, 1.0mm, 1.1mm, or 1.2mm.

87. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, The drop ball test height II of the photosensitive microcrystalline glass product is above 800mm.

88. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, The drop ball test height II of the photosensitive microcrystalline glass product is above 900 mm.

89. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, The drop ball test height II of the photosensitive microcrystalline glass product is above 1000mm.

90. The photosensitive microcrystalline glass article according to any one of claims 55 to 58, characterized in that, The drop ball test height II of the photosensitive microcrystalline glass product is above 1100mm.

91. A glass cover plate, characterized in that, The product contains the photosensitive glass according to any one of claims 1 to 22, and / or the photosensitive microcrystalline glass according to any one of claims 23 to 54, and / or the photosensitive microcrystalline glass article according to any one of claims 55 to 90.

92. A glass component, characterized in that, The product contains the photosensitive glass according to any one of claims 1 to 22, and / or the photosensitive microcrystalline glass according to any one of claims 23 to 54, and / or the photosensitive microcrystalline glass article according to any one of claims 55 to 90.

93. A device, characterized in that, The invention comprises the photosensitive glass according to any one of claims 1 to 22, and / or the photosensitive microcrystalline glass according to any one of claims 23 to 54, and / or the photosensitive microcrystalline glass article according to any one of claims 55 to 90, and / or the glass cover plate according to claim 91, and / or the glass component according to claim 92.

94. A method for manufacturing the photosensitive microcrystalline glass according to any one of claims 23 to 54, characterized in that, The method includes the following steps: forming photosensitive glass, and then forming photosensitive microcrystalline glass by crystallization process.

95. The method for manufacturing photosensitive microcrystalline glass according to claim 94, characterized in that, The crystallization process includes mask exposure of the photosensitive glass, followed by crystallization heat treatment. The mask exposure process includes ultraviolet exposure of specific locations or areas of the photosensitive glass.

96. The method for manufacturing photosensitive microcrystalline glass according to claim 94, characterized in that, The crystallization process includes mask exposure of the photosensitive glass, followed by crystallization heat treatment. The mask exposure process includes ultraviolet exposure of a specific location or area of ​​the photosensitive glass, with an ultraviolet wavelength of 280–360 nm and an exposure time of 5–60 minutes.

97. The method for manufacturing photosensitive microcrystalline glass according to claim 94, characterized in that, The crystallization process includes mask exposure of the photosensitive glass, followed by crystallization heat treatment. The mask exposure process includes ultraviolet exposure of a specific location or area of ​​the photosensitive glass, with an ultraviolet wavelength of 300-330 nm and an exposure time of 5-60 minutes.

98. The method for manufacturing photosensitive microcrystalline glass according to claim 94, characterized in that, The crystallization process includes mask exposure of the photosensitive glass, followed by crystallization heat treatment. The mask exposure process includes ultraviolet exposure of a specific location or area of ​​the photosensitive glass with an ultraviolet wavelength of 313 nm and an exposure time of 5 to 60 minutes.

99. The method for manufacturing photosensitive microcrystalline glass according to claim 95, characterized in that, The crystallization heat treatment is carried out in two stages. The two-stage crystallization heat treatment includes nucleation process at a first temperature and crystal growth process at a second temperature higher than the nucleation process temperature.

100. The method for manufacturing photosensitive microcrystalline glass according to claim 95, characterized in that, The crystallization heat treatment is carried out in two stages. The two-stage crystallization heat treatment includes nucleation process at a first temperature and crystal growth process at a second temperature higher than the nucleation process temperature. The first temperature is 490℃~520℃ and the treatment time is 1~4 hours. The second temperature is 540℃~620℃ and the treatment time is 1~8 hours.

101. A method for manufacturing a photosensitive microcrystalline glass article according to any one of claims 55 to 90, characterized in that, The method includes the following steps: forming photosensitive glass, forming photosensitive microcrystalline glass through a crystallization process, and then forming a photosensitive microcrystalline glass product through a chemical strengthening process.

102. The method for manufacturing a photosensitive microcrystalline glass article according to claim 101, characterized in that, The crystallization process includes mask exposure of the photosensitive glass, followed by crystallization heat treatment. The mask exposure process includes ultraviolet exposure of specific locations or areas of the photosensitive glass.

103. The method for manufacturing a photosensitive microcrystalline glass article according to claim 101, characterized in that, The crystallization process includes mask exposure of the photosensitive glass, followed by crystallization heat treatment. The mask exposure process includes ultraviolet exposure of a specific location or area of ​​the photosensitive glass, with an ultraviolet wavelength of 280–360 nm and an exposure time of 5–60 minutes.

104. The method for manufacturing a photosensitive microcrystalline glass article according to claim 101, characterized in that, The crystallization process includes mask exposure of the photosensitive glass, followed by crystallization heat treatment. The mask exposure process includes ultraviolet exposure of a specific location or area of ​​the photosensitive glass, with an ultraviolet wavelength of 300-330 nm and an exposure time of 5-60 minutes.

105. The method for manufacturing a photosensitive microcrystalline glass article according to claim 101, characterized in that, The crystallization process includes mask exposure of the photosensitive glass, followed by crystallization heat treatment. The mask exposure process includes ultraviolet exposure of a specific location or area of ​​the photosensitive glass with an ultraviolet wavelength of 313 nm and an exposure time of 5 to 60 minutes.

106. The method for manufacturing a photosensitive microcrystalline glass article according to claim 102, characterized in that, The crystallization heat treatment is carried out in two stages, which includes nucleation at a first temperature and crystal growth at a second temperature higher than the nucleation temperature.

107. The method for manufacturing a photosensitive microcrystalline glass article according to claim 102, characterized in that, The crystallization heat treatment is carried out in two stages. The two-stage crystallization heat treatment includes nucleation process at a first temperature and crystal growth process at a second temperature higher than the nucleation process temperature. The first temperature is 490℃~520℃ and the treatment time is 1~4 hours. The second temperature is 540℃~620℃ and the treatment time is 1~8 hours.

108. The method for manufacturing a photosensitive microcrystalline glass article according to claim 101, characterized in that, The chemical strengthening process includes immersing the photosensitive microcrystalline glass in a salt bath of molten Na salt, and / or K salt, and / or a mixed Na and K salt at a temperature of 350°C to 470°C for 1 to 36 hours at a temperature of 380°C to 460°C.

109. The method for manufacturing a photosensitive microcrystalline glass article according to claim 101, characterized in that, The chemical strengthening process involves immersing the photosensitive microcrystalline glass in a salt bath of a mixture of Na and K for 2 to 24 hours at a temperature of 380°C to 460°C.

Citation Information

Patent Citations

  • Photoformable glass-ceramics comprising nepheline crystal phases

    CN107810167A

  • Photosensitive glasses and glass ceramics and composite glass materials made therefrom

    CN108698910A

  • Glass cover plate, preparation method thereof and touch screen

    CN109896729A

  • Photosensitive microcrystalline glass

    CN114933416A